Thin film, hard coating film, method for producing both, image display device, and touch panel

By controlling the vertical stress on the shear surface and laminated hardcoat layer on the polyester film, the problems of the film being recessed and hardcoat layer ruptured under load conditions are solved, achieving higher durability and visibility.

CN119431857APending Publication Date: 2025-02-14FUJIFILM CORP
View PDF 83 Cites 0 Cited by

Patent Information

Application Number
CN202311359777.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-02-15
Filing Date
2017-01-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing polyester films are prone to depression when locally applied to loads along the thickness direction and may cause cracking or peeling during hard coating die cutting.

Method used

The polyester film with a thickness of 40 to 500 μm was used, and the average value between the shear surface vertical stress in the slow-axis direction and the shear surface vertical stress in the fast-axis direction was 30 to 100 MPa, and was laminated on the film. Hard coating, the hard coating comprises at least a compound of a specific structural composition.

Benefits of technology

It effectively inhibits the film from being recessed under load conditions, and prevents cracking or peeling of the hard coating during punching and cutting, improving the visibility and durability of the image display device and touch panel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431857A_ABST
    Figure CN119431857A_ABST
Patent Text Reader

Abstract

The invention provides a thin film, a hard coating film, a manufacturing method of the thin film and the hard coating film, an image display device and a touch panel. The thickness of the polyester film is 40-500 [mu] m, and the average value of the shear plane vertical stress A in the slow axis direction at the surface layer of 1 [mu] m and the shear plane vertical stress B in the direction orthogonal to the slow axis direction in the film plane is 30-100 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The international application number of the original application is PCT / JP2017 / 003241, the Chinese national application number is 201780010643.6, the application date is January 30, 2017, and the name of the invention is "Polyester film and its manufacturing method, hard coating film and its manufacturing method, image display device and touch panel". Technical Field

[0002] The present invention relates to a polyester film and a method for producing the same, a hard coating film and a method for producing the same, an image display device and a touch panel. Background Art

[0003] In applications using chemically strengthened glass, as the technology of increasing the hardness of hard coating materials has progressed, hard coating films in which a hard coating layer is laminated on a substrate film have attracted attention as glass replacement. An example of a hard coating film is the outermost protective film of an image display device such as a touch panel.

[0004] For example, Patent Document 1 discloses “a laminate substrate having a functional layer formed on one surface to form a laminate, the laminate substrate comprising:

[0005] A light-transmitting substrate having in-plane birefringence;

[0006] The refractive index adjusting layer is laminated with the light-transmitting substrate and has in-plane birefringence and is located between the light-transmitting substrate and the functional layer.

[0007] The refractive index n in the direction of the slow axis, i.e., the direction in which the refractive index in the plane of the light-transmitting substrate is the largest, is 1x , the refractive index n of the refractive index adjustment layer in the direction parallel to the slow axis direction of the light-transmitting substrate 2x and the refractive index n of the functional layer in the direction parallel to the slow axis direction of the light-transmitting substrate 3x The following relations are satisfied:

[0008] n 1x <n 2x <n 3x or 1x >n 2x >n 3x

[0009] The refractive index n in the fast axis direction perpendicular to the slow axis direction of the light-transmitting substrate is 1y , the refractive index n of the refractive index adjustment layer in the direction parallel to the fast axis direction of the light-transmitting substrate 2y and the refractive index n of the functional layer in a direction parallel to the fast axis direction of the light-transmitting substrate 3y The following relations are satisfied:

[0010] n 1y <n2y <n 3y or 1y >n 2y >n 3y ”.

[0011] Patent document 2 discloses "a surface protection film characterized in that it has a laminated structure of at least three layers, the softening points of the two outermost polyester layers are higher than the softening point of the middle layer, the surface protection film is a surface protection film in which coating layers are formed on both sides of a multilayer polyester film and an adhesive layer is provided on the surface of one coating layer, and the coating layer is formed by a coating liquid containing 70% by weight or more of a cross-linking agent relative to a non-volatile component."

[0012] Patent Document 3 discloses "a uniaxially oriented polyester film having the following characteristics:

[0013] (1) On the surface of the film, scratches with a height difference of more than 1 μm are located every 1 m. 2 There is less than 1 scratch per 1m, and the height difference is more than 0.3μm and less than 1μm. 2 The number of items is less than 20.

[0014] (2) In the film, foreign matter with a long diameter of 100 μm or more is present in every 1 m 2 There are less than 1 in the

[0015] (3) the three-dimensional average surface roughness (SRa) of the film surface is in the range of 0.020 to 0.060 μm, and

[0016] (4) The maximum strain of the orientation axis of the film measured by a microwave transmission type molecular orientation meter is within 7 degrees.

[0017] Patent document 4 discloses "a uniaxially oriented laminated polyester film, which is a uniaxially oriented coextruded laminated film composed of at least three polyester layers of layer A, layer B and layer C, characterized in that layer A and layer C as the outermost layers are composed of substantially homopolymerized polyester containing 0.01 to 0.5% by weight of inert particles with an average particle size of 0.1 to 5.0 μm, layer B as the intermediate layer is composed of a polyester having a dicarboxylic acid component, an aliphatic or alicyclic diol component and a polyalkylene ether glycol component with a number average molecular weight of 300 to 4000 as main components and containing 10 to 35% by weight of the polyalkylene ether glycol component, and the thickness ratio of layer B in the total film thickness is 65 to 95%."

[0018] Patent Document 5 discloses “a polyester film satisfying the following formula;

[0019] 0m≤C S <0.003L 2 / 8W

[0020] 0m≤C CT <0.003L 2 / 4W

[0021] 0.8m≤W≤6.0m

[0022] 20m≤L≤30m

[0023] In the formula, C S [Unit: m] represents the total width arc value of the film, C CT [Unit: m] indicates the value of the half-cut arc at the center of the film width direction, W [Unit: m] indicates the film width, and L [Unit: m] indicates the film length when measuring the total width arc and the half-cut arc. ".

[0024] Previous technical literature

[0025] Patent Literature

[0026] Patent Document 1: Japanese Patent Application Publication No. 2013-257550

[0027] Patent Document 2: Japanese Patent Application Publication No. 2015-128897

[0028] Patent Document 3: Japanese Patent Application Publication No. 2005-2220

[0029] Patent Document 4: Japanese Patent Application Publication No. 2004-351788

[0030] Patent Document 5: International Publication No. 2015 / 46122 Summary of the invention

[0031] Technical issues to be solved by the invention

[0032] The films disclosed in Patent Documents 1 to 5 have insufficient stress perpendicular to the shear plane, and are prone to depression when a load is locally applied in the thickness direction of the film. It is believed that if a hard coating film having a hard coating layer laminated on these films is manufactured and punched, the hard coating layer is prone to cracking or peeling.

[0033] An object of the present invention is to provide a polyester film which is less likely to be dented even when a load is locally applied in the thickness direction of the film, and a method for producing the same.

[0034] Another object of the present invention is to provide a hard coat film in which a hard coat layer is laminated on a polyester film and the hard coat layer is not easily cracked or peeled off during punching, and a method for producing the same.

[0035] Another object of the present invention is to provide an image display device and a touch panel that can suppress a decrease in visibility due to rainbow unevenness even when a load is locally applied to a display screen.

[0036] Means for solving technical problems

[0037] In order to achieve the above object, the following method is provided.

[0038] <1> A polyester film having a thickness of 40 to 500 μm and an average value of a shear plane perpendicular stress A in the slow axis direction at 1 μm from the surface layer and a shear plane perpendicular stress B in a direction perpendicular to the slow axis direction in the film surface of 30 to 100 MPa.

[0039] <2> according to <1> The polyester film is a film used as a base film of a hard coating film.

[0040] <3> according to <1> or <2> The polyester film is a uniaxially oriented polyester film.

[0041] <4> according to <1> ~ <3> The polyester film according to any one of the preceding claims, wherein the retardation Re within the film plane of the polyester film at a measurement wavelength of 589 nm is 4,000 to 50,000 nm.

[0042] <5> according to <1> ~ <4> The polyester film according to any one of the preceding claims, wherein the average value of the shear plane yield stress in the slow axis direction at 1 μm in the surface layer of the polyester film and the shear plane yield stress in the direction perpendicular to the slow axis direction in the film plane is 20 to 60 MPa.

[0043] <6> according to <1> ~ <5> The polyester film according to any one of the preceding claims, wherein a ratio of a shear plane perpendicular stress A to a shear plane perpendicular stress B is 1.1 to 2.0.

[0044] <7> according to <1> ~ <6> The polyester film according to any one of the preceding claims, wherein the ratio of the retardation Re in the film plane to the retardation Rth in the film thickness direction at a measurement wavelength of 589 nm is 0.6 to 1.2.

[0045] <8> A hard coating film having:

[0046] Base film, including <1> ~ <7> The polyester film described in any one of the above; and

[0047] The hard coat layer is laminated on at least one side of the base film.

[0048] <9> according to <8> The hard coating film has a hard coating layer having a thickness of 5 μm or more.

[0049] <10> according to <8> or <9> The hard coating film, wherein

[0050] The hard coat layer includes at least a structure derived from the following a), a structure derived from the following b), the following c) and the following d),

[0051] When the total solid content of the hard coat layer is 100 mass %, the hard coat layer contains 15 to 70 mass % of a structure derived from the following a), 25 to 80 mass % of a structure derived from the following b), 0.1 to 10 mass % of the following c), and 0.1 to 10 mass % of the following d).

[0052] a) A compound having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less

[0053] b) A compound having three or more groups containing ethylenically unsaturated double bonds in the molecule

[0054] c) Free Radical Polymerization Initiator

[0055] d) Cationic polymerization initiator

[0056] <11> An image display device comprises an image display element and <8> ~ <10> In any one of the above hard coating films, the hard coating film is disposed on the outermost surface.

[0057] <12> A touch panel comprising <8> ~ <10> In any one of the above hard coating films, the hard coating film is disposed on the outermost surface.

[0058] <13> A method for producing a polyester film, wherein the polyester film has a thickness of 40 to 500 μm and uses a transverse stretching device having a plurality of clamps, wherein the plurality of clamps respectively travel along a pair of rails provided on both sides of a film conveying path.

[0059] The manufacturing method comprises:

[0060] A preheating process, preheating the unstretched or longitudinally stretched polyester film at a heating rate of less than 600°C / min;

[0061] a transverse stretching step, in which the preheated polyester film is stretched in a direction perpendicular to the film conveying path while holding both edges of the film with a plurality of clamps, and the surface temperature of the polyester film is gradually increased from the start of the transverse stretching to the end of the transverse stretching, the surface temperature at the start of the transverse stretching is controlled to be 80° C. to 95° C., and the surface temperature at the end of the transverse stretching is controlled to be 90° C. to 105° C., and the transverse stretching ratio is controlled to be within a range of 3.3 times to 4.8 times; and

[0062] In the heat setting step, the polyester film after the transverse stretching step is heated to the maximum temperature in the transverse stretching device to perform heat setting.

[0063] <14> according to <13> The method for producing the polyester film, wherein:

[0064] In the transverse stretching process, the surface temperature is gradually increased at a heating rate of 60°C / min or less.

[0065] When the transverse stretching ratio is in the range of 1 to 2, the surface temperature is controlled to be 80°C to 92°C.

[0066] The surface temperature is controlled to be 85°C to 97°C when the transverse stretching ratio is in the range of 2 to 3 times, and

[0067] When the transverse stretch ratio is in the range of 3 times or more, the surface temperature is controlled to be 90° C. or more and 102° C. or less.

[0068] <15> according to <13> or <14> The method for producing the polyester film, wherein:

[0069] The rate of increase in the surface temperature of the polyester film from the end of the transverse stretching step to the maximum temperature in the heat setting step is controlled to be 1000°C / min or less.

[0070] The highest surface temperature of the polyester film in the heat setting step is controlled to be 130° C. or higher and 230° C. or lower, and the time during which the surface temperature of the polyester film exceeds 130° C. is controlled to be 180 seconds or less.

[0071] <16> according to <13> ~ <15> The method for producing a polyester film as described above further comprises a heat relaxation step of heating the polyester film after the heat setting step to reduce at least the transverse length of the polyester film.

[0072] <17> A method for producing a hard coating film, comprising:

[0073] pass <13> ~ <16> The method for producing a polyester film according to any one of the preceding claims, comprising a step of producing a polyester film; and

[0074] A step of laminating a hard coat layer on at least one side of the polyester film.

[0075] Effects of the Invention

[0076] According to the present invention, it is possible to provide a polyester film which is unlikely to be dented even when a load is locally applied in the thickness direction of the film, and a method for producing the same.

[0077] Furthermore, according to the present invention, it is possible to provide a hard coat film in which a hard coat layer is laminated on a polyester film and the hard coat layer is less likely to be cracked or peeled off during punching, and a method for producing the same.

[0078] Furthermore, according to the present invention, it is possible to provide an image display device and a touch panel that can suppress a decrease in visibility due to rainbow unevenness even when a load is locally applied to a display screen. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 This is a perspective view showing an example of a cutting insert used in a method for measuring the shear plane perpendicular stress and the shear plane yield stress of a thin film surface layer.

[0080] Figure 2 This is a schematic diagram for explaining the method of measuring the shear plane perpendicular stress and shear plane yield stress of the film surface.

[0081] Figure 3 It is a schematic diagram showing an example of the structure of a transverse stretching device. DETAILED DESCRIPTION

[0082] The present invention is described in detail below. The description of the constituent elements described below is sometimes based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In addition, in this specification, the numerical range represented by "to" refers to a range that includes the numerical values ​​described before and after the "to" as the lower limit and the upper limit. And, when one of the numerical values ​​described before and after the "to" is marked with a unit, it means that it is the same unit throughout the numerical range.

[0083] [Polyester film]

[0084] The polyester film (hereinafter also referred to as "film") involved in this embodiment has a thickness of 40 to 500 μm, and the average value of the shear plane perpendicular stress A in the slow axis direction at 1 μm of the surface layer and the shear plane perpendicular stress B in the direction orthogonal to the slow axis direction in the film surface is 30 to 100 MPa.

[0085] Here, the “slow axis direction” of the film refers to the direction in which the refractive index is the largest within the film plane, and the direction orthogonal to the slow axis direction within the film plane is also referred to as the “fast axis direction”.

[0086] The method for producing the polyester film according to the present embodiment will be described in detail later. For example, after the polyester resin composition is melt-extruded into a film, it is conveyed using a roller or the like, and the polyester film is produced by stretching at least in a direction (also referred to as the width direction or transverse direction of the film) perpendicular to the conveying direction of the film (also referred to as the length direction or longitudinal direction of the film). The width direction of the film is usually the slow axis direction. In addition, when the polyester film is produced as described above, the conveying direction of the film is sometimes referred to as MD (Machine Direction), and the direction perpendicular to the conveying direction of the film is sometimes referred to as TD (Transverse Direction).

[0087] <Characteristics of polyester film>

[0088] (thickness)

[0089] The thickness of the polyester film according to the present embodiment is 40 to 500 μm.

[0090] When the thickness of the polyester film is 40 μm or more, it has sufficient rigidity and can be easily used as a glass substitute. When the thickness is 500 μm or less, the rigidity is not too high and the punching property and handling property of the film are good.

[0091] From this viewpoint, the thickness of the polyester film according to the present embodiment is more preferably 60 to 400 μm, and further preferably 80 to 300 μm.

[0092] In addition, regarding the thickness of the polyester film involved in this embodiment, for example, using a contact film thickness meter, samples are taken at 50 locations in the slow axis direction of the film and in a direction orthogonal to the slow axis direction within the film surface, and the average thickness of the measured thickness values ​​at the locations is calculated as the thickness of the polyester film.

[0093] (Stress perpendicular to shear plane)

[0094] The average value of the shear plane perpendicular stress A in the slow axis direction at 1 μm of the surface layer of the polyester film involved in this embodiment and the shear plane perpendicular stress B in the direction orthogonal to the slow axis direction in the film surface (hereinafter, sometimes referred to as "surface average shear plane perpendicular stress".) is 30 to 100 MPa. Here, "surface layer 1 μm" refers to the area from the surface of the polyester film to a depth of 1 μm.

[0095] If the average surface shear plane perpendicular stress at 1 μm of the surface layer is 30 MPa or more, when a hard coating layer is laminated on a polyester film to form a hard coating film, it is not easy for dents to occur on the film when the film is pressed strongly. If it is 100 MPa or less, when a hard coating film is formed, it is not easy for cracks or peeling to occur in the hard coating layer.

[0096] From this viewpoint, the average shear plane perpendicular stress of the surface layer of the polyester film according to the present embodiment is preferably 40 to 90 MPa, more preferably 50 to 80 MPa.

[0097] Furthermore, in the polyester film according to the present embodiment, the ratio (A / B) of the shear plane perpendicular stress A to the shear plane perpendicular stress B is preferably 1.1 to 2.0.

[0098] If the ratio A / B of the perpendicular stress on the shear plane in the polyester film involved in this embodiment is greater than 1.1, it is easy to manufacture a uniaxially oriented polyester film that can suppress rainbow-shaped unevenness. If it is less than 2.0, when a hard coating layer is stacked on the polyester film to form a hard coating film, cracks or peeling are not likely to occur in the hard coating layer.

[0099] From this viewpoint, the ratio A / B of the stress perpendicular to the shear plane of the polyester film according to the present embodiment is more preferably 1.2 to 1.9, and further preferably 1.3 to 1.8.

[0100] (Shear plane yield stress)

[0101] In the polyester film involved in the present embodiment, the average value of the shear plane yield stress in the slow axis direction at 1 μm of the surface layer and the shear plane yield stress in the direction orthogonal to the slow axis direction in the film surface (hereinafter, sometimes referred to as "surface average shear plane yield stress") is preferably 20 to 60 MPa. If the surface average shear plane yield stress of the polyester film involved in the present embodiment is 20 MPa or more, when a hard coating layer is laminated on the polyester film to form a hard coating film, even if the film is pressed with force, it is not easy to generate depressions in the film. If it is 60 MPa or less, when a hard coating film is formed, it is not easy to generate cracks or peeling in the hard coating layer.

[0102] From this viewpoint, the surface layer average shear plane yield stress of the polyester film according to the present embodiment is more preferably 25 to 55 MPa, further preferably 30 to 50 MPa.

[0103] Here, the measurement of the shear plane perpendicular stress and the shear plane yield stress of the film surface layer in this embodiment will be described. Figure 1 and Figure 2 This is a schematic diagram for explaining the method of measuring the shear plane perpendicular stress and shear plane yield stress of the film surface. The measuring device, measuring conditions, and calculation method of the shear plane perpendicular stress and shear plane yield stress are as follows.

[0104] (1) Measurement device

[0105] In the present embodiment, the shear plane vertical stress and shear plane yield stress of the film surface layer are measured using SAICAS (Surface And Interfacial Cutting Analysis System)-NN type (manufactured by DAIPLA WINTES CO., LTD.). SAICAS can control the cutting blade speed and monitor the vertical force Fv and horizontal force FH applied to the cutting blade 10, and the vertical displacement d of the cutting blade.

[0106] (2) Measurement conditions

[0107] First, the rake angle α and the relief angle (cutting angle) γ of the cutting blade 10 relative to the surface of the film 12 are set to predetermined angles, and the cutting blade is used to cut from the surface of the film to the inside ( Figure 1 (A)).

[0108] The cutting force ( Figure 1 (B)).

[0109] The stress (film strength) acting on the shear surface by cutting into the surface layer of the thin film 12 to a depth of 1 μm was evaluated. Figure 1 (C)).

[0110] Here, the measurement conditions are as follows.

[0111] Cutting speed: horizontal speed 100nm / s, vertical speed 10nm / s

[0112] Blade width: 0.1mm

[0113] Rake angle α: 20°

[0114] Cutting angle γ: 10°

[0115] Blade type: Diamond cutting blade

[0116] Direction: Measure in the slow axis direction and the fast axis direction (TD, MD)

[0117] Measurements were made at three locations at intervals of 10 mm in each direction, and the average value was taken as the value in each direction.

[0118] (3) Calculation of shear plane vertical stress and shear plane yield stress

[0119] exist Figure 2 The cutting blade with rake angle α is shown in Figure 1 The direction of the force acting when the sample (polyester film) 12 is cut at a cutting angle γ is (A) toward (C). H and the vertical force F V , shear angle φ, the force F acting parallel to the shear plane AB of the specimen is calculated as follows: S and the vertical force F N .

[0120] Formula (1)

[0121] [Formula 1]

[0122] F S =F H cosφ-F V sinφ

[0123] F N =F H sinφ+F V coSφ

[0124] F S and F N Divide by the area of ​​the shear surface A s , respectively, as in formula (2) to find the shear surface ( Figure 2 The stress (τ s ; Shear plane yield stress) and the stress acting perpendicularly (σ s ; stress perpendicular to the shear plane). In addition, b is the blade width and d is the cutting depth (vertical displacement).

[0125] Formula (2)

[0126] [Formula 2]

[0127]

[0128]

[0129] Furthermore, the shear angle φ is calculated as shown in the following formula (3) using the rake angle α and the friction angle β.

[0130] Formula (3)

[0131] [Formula 3]

[0132]

[0133] That is, by calculating the horizontal force F at each depth H and the vertical force F V By finding the shear angle α, the shear surface yield stress τ can be calculated s Or the shear plane perpendicular stress σ s The depth distribution of .

[0134] The polyester film according to the present embodiment is preferably a uniaxially oriented polyester film. A polyester film having the above-mentioned thickness and perpendicular shear stress can be easily obtained by transversely stretching and heat-setting an unstretched polyester film produced by melt film or solution film by the method described below.

[0135] -Re(Retardation in the film plane)-

[0136] In the polyester film according to the present embodiment, the retardation Re within the film plane at a measurement wavelength of 589 nm is preferably 4,000 to 50,000 nm.

[0137] When the Re of the polyester film according to the present embodiment is 4000 nm or more, rainbow unevenness is less likely to be visually recognized, and when it is 50000 nm or less, the required film thickness is not too thick, and excessive rigidity can be suppressed, making handling easy.

[0138] From this viewpoint, the Re of the polyester film according to the present embodiment at a measurement wavelength of 589 nm is more preferably 5000 to 40000 nm, and further preferably 7000 to 33000 nm.

[0139] -Re / Rth-

[0140] Furthermore, the polyester film according to the present embodiment preferably has a ratio (Re / Rth) of the retardation Re within the film plane to the retardation Rth in the film thickness direction at a measurement wavelength of 589 nm of 0.6 to 1.2.

[0141] When the Re / Rth of the polyester film according to the present embodiment at a measurement wavelength of 589 nm is 0.6 or more, rainbow unevenness is less likely to be visually recognized, and when it is 1.2 or less, the film is less likely to become brittle.

[0142] From this viewpoint, Re / Rth of the polyester film according to the present embodiment is more preferably 0.7 to 1.15, further preferably 0.8 to 1.1.

[0143] The retardation Rth of the polyester film in the thickness direction at a measurement wavelength of 589 nm according to the present embodiment is preferably 3000 to 80000 nm, more preferably 4000 to 60000 nm, and further preferably 6000 to 40000 nm. If Rth is 3000 nm or more, it is easy to make a film, and if it is 80000 nm or less, when a hard coating film using the polyester film according to the present embodiment is applied to a display screen of an image display device, rainbow unevenness is not easily generated on the screen, so it is preferred.

[0144] Rainbow unevenness can also be reduced by setting the Nz value representing the relationship between Re and Rth to an appropriate value. Based on the effect of reducing rainbow unevenness and manufacturing adaptability, the absolute value of the Nz value is preferably 2.0 or less, more preferably 0.5 to 2.0, and further preferably 0.5 to 1.5.

[0145] Rainbow-like unevenness is caused by incident light and is therefore usually observed during white displays.

[0146] The film-plane retardation Re of the polyester film according to the present embodiment is represented by the following formula (4).

[0147] Formula (4): Re = (nx - ny) × y1

[0148] Here, nx is the refractive index of the polyester film in the in-plane slow axis direction, ny is the refractive index of the polyester film in the in-plane fast axis direction (direction perpendicular to the in-plane slow axis direction), and y1 is the thickness of the polyester film.

[0149] The retardation Rth in the thickness direction of the polyester film according to the present embodiment is represented by the following formula (5).

[0150] Formula (5): Rth={(nx+ny) / 2-nz}×y1

[0151] Here, nz is the refractive index in the thickness direction of the polyester film.

[0152] In addition, the Nz value of the polyester film is represented by the following formula.

[0153] Nz=(nx-nz) / (nx-ny)

[0154] In this specification, Re, Rth, and Nz at a wavelength λ nm can be measured as follows.

[0155] Use two polarizing plates to find out the orientation axis directions (slow axis direction and fast axis direction) of the polyester film, and cut out a 4cm×2cm rectangle in a way that the orientation axis directions are orthogonal to each other as a sample for measurement. For this sample, the refractive index (Nx, Ny) of the two orthogonal axes and the refractive index (Nz) in the thickness direction are found by an Abbe refractometer (manufactured by ATAGO CO., LTD., NAR-4T, measurement wavelength 589nm), and the absolute value of the refractive index difference between the two axes (|Nx-Ny|) is used as the anisotropy of the refractive index (ΔNxy). The thickness y1 (nm) of the polyester film is measured using an electric micrometer (manufactured by Fine Liu off Corp., Miritoron 1245D), and the unit is converted to nm. Re, Rth, and Nz are calculated from the measured values ​​of Nx, Ny, Nz, and y1, respectively.

[0156] The Re and Rth can be adjusted by the type of polyester resin used in the film, the amounts of the polyester resin and additives, the addition of a retardation developer, the film thickness, the stretching direction and stretching ratio of the film, and the like.

[0157] The method for controlling Re and Re / Rth of the polyester film according to the present embodiment within respective ranges is not particularly limited, and can be achieved, for example, by a stretching method.

[0158] <Structural materials, layer structure and surface treatment of polyester film>

[0159] The polyester film according to the present embodiment contains a polyester resin, and the mass ratio of the polyester resin in the entire film is usually 50 mass % or more, preferably 70 mass % or more, and more preferably 90 mass % or more.

[0160] The polyester film according to the present embodiment may be a single-layer film having a layer containing a polyester resin as a main component, or may be a multi-layer film having at least one layer containing a polyester resin as a main component.

[0161] Furthermore, the polyester film of this embodiment may be subjected to surface treatment on both sides or one side of the film. The surface treatment may be surface modification based on corona treatment, saponification treatment, heat treatment, ultraviolet irradiation, electron beam irradiation, etc., or film formation based on coating, vapor deposition, etc. of polymers, metals, etc.

[0162] The polyester film according to the present embodiment may have an easily adhesive layer on at least one surface.

[0163] The thickness of the easily adhesive layer included in the polyester film according to the present embodiment is preferably 30 to 300 nm, more preferably 40 to 200 nm, and further preferably 50 to 150 nm.

[0164] If the thickness of the easy-adhesion layer is 30 nm or more, the buffering effect based on the easy-adhesion layer is easily obtained, and the shear plane vertical stress and the shear plane yield stress can be suppressed from excessively increasing. In addition, if the thickness of the easy-adhesion layer is 300 nm or less, the buffering effect of the easy-adhesion layer will not be too strong, and the shear plane vertical stress and the shear plane yield stress can be suppressed from excessively decreasing.

[0165] More preferably, the easily bonding layer contains particles, and the height of the particles protruding from the surface of the easily bonding layer is equal to or greater than the film thickness of the easily bonding layer.

[0166] The height of the particles protruding from the surface of the easy-adhesion layer was an average value of five locations in the easy-adhesion layer having a size of 1 mm square.

[0167] If the height of the particles contained in the easy adhesion layer protruding from the surface of the easy adhesion layer is lower than the film thickness of the easy adhesion layer (preferably the coating layer), the sliding property is reduced and wrinkles tend to be easily generated.

[0168] The type of particles is not particularly limited. As specific examples, for example, particles such as silicon dioxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, titanium oxide, and zirconium oxide can be cited, preferably silicon dioxide, aluminum oxide, titanium oxide, and zirconium oxide. In addition, heat-resistant organic particles described in Japanese Patent Publication No. 59-5216 and Japanese Patent Publication No. 59-217755 can also be used. As examples of other heat-resistant organic particles, thermosetting urea resins, thermosetting phenolic resins, thermosetting epoxy resins, benzoguanamine resins, etc. can be cited.

[0169] Regarding the particle size, it is preferred that the particle protrudes from the surface of the easy bonding layer to a particle size greater than the thickness of the easy bonding layer. It is preferred to use particles adjusted with a primary average particle size, and as a result, it can be particles that are condensed into particles protruding from the surface of the easy bonding layer to a particle thickness greater than the thickness of the easy bonding layer. In the case of condensed particles, by measuring the secondary average particle size, it is possible to confirm the height of the particle protruding from the surface of the easy bonding layer.

[0170] (1-1) Polyester resin

[0171] As the polyester resin contained in the polyester film according to the present embodiment, for example, a polyester resin having the composition

[0042] of WO2012 / 157662 is preferably used.

[0172] As specific polyester resins, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polycyclohexane dimethyl terephthalate (PCT), etc. can be used, but in terms of cost and heat resistance, PET and PEN are more preferred, and PET is further preferred. In addition, the Re / Rth of PEN is slightly easier to become smaller.

[0173] As the polyester resin, polyethylene terephthalate is most preferred, but polyethylene naphthalate can also be preferably used. For example, polyethylene naphthalate described in Japanese Patent Application Laid-Open No. 2008-39803 can also be preferably used.

[0174] Polyethylene terephthalate is a polyester having a structural unit derived from terephthalic acid as a dicarboxylic acid component and a structural unit derived from ethylene glycol as a diol component, preferably 80 mol% or more of the total repeating units are ethylene terephthalate, and may also contain structural units derived from other copolymer components. As other copolymer components, dicarboxylic acid components such as isophthalic acid, p-β-oxyethoxybenzoic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-dicarboxybenzophenone, bis(4-carboxyphenyl)ethane, adipic acid, sebacic acid, isophthalic acid-5-sulfonic sodium, 1,4-cyclohexanedicarboxylic acid, and diol components such as propylene glycol, butanediol, neopentyl glycol, diethylene glycol, cyclohexanediol, ethylene oxide adducts of bisphenol A, polyethylene glycol, polypropylene glycol, polybutylene glycol can be cited. These dicarboxylic acid components or diol components can be used in combination of two or more as needed. Furthermore, hydroxycarboxylic acids such as p-hydroxybenzoic acid can also be used together with the above-mentioned carboxylic acid components or diol components. As other copolymerization components, dicarboxylic acid components and / or diol components containing a small amount of amide bonds, urethane bonds, ether bonds, carbonate bonds, etc. can be used.

[0175] As a method for producing polyethylene terephthalate, any production method can be applied, such as a so-called direct polymerization method in which terephthalic acid is directly reacted with ethylene glycol and, if necessary, other dicarboxylic acids and / or other diols, or a so-called transesterification method in which dimethyl terephthalate is subjected to an ester exchange reaction with ethylene glycol and, if necessary, other dicarboxylic acids and / or other diols.

[0176] (1-2) Physical properties of polyester resin

[0177] (1-2-1) Intrinsic viscosity

[0178] The intrinsic viscosity IV of the polyester resin is preferably 0.5 to 0.9, more preferably 0.52 to 0.8, and further preferably 0.54 to 0.7. To achieve such an IV, solid phase polymerization may be used simultaneously in addition to melt polymerization described below when synthesizing the polyester resin.

[0179] (1-2-2) Acetaldehyde content

[0180] The acetaldehyde content of the polyester resin is preferably 50 ppm or less. It is further preferably 40 ppm or less, and particularly preferably 30 ppm or less. Acetaldehyde easily causes a condensation reaction between acetaldehydes to generate water as a side reaction product, and the polyester is sometimes hydrolyzed by the water. The lower limit of the acetaldehyde content is about 1 ppm in reality. In order to set the acetaldehyde content within the above range, it is possible to adopt methods such as keeping the oxygen concentration in each process such as melt polymerization and solid phase polymerization at a low level when manufacturing the resin, keeping the oxygen concentration at a low level when storing and drying the resin, reducing the heat history applied to the resin in the extruder, melt piping, mold, etc. when manufacturing the film, and preventing strong shearing from being locally applied in the screw structure of the extruder during melting.

[0181] (1-3) Catalyst

[0182] In the polymerization of the polyester resin, a Sb, Ge, Ti and / or Al-based catalyst is used, preferably a Sb, Ti and / or Al-based catalyst, and more preferably an Al-based catalyst.

[0183] That is, the polyester resin used as the raw material resin is preferably a resin obtained by polymerization using an aluminum catalyst.

[0184] By using an Al-based catalyst, Re is more likely to be expressed than when other catalysts (such as Sb or Ti) are used, and PET can be made thinner. In other words, it means that orientation is easier when using an Al-based catalyst. This is inferred to be based on the following reasons.

[0185] Compared with Sb-based catalysts or Ti-based catalysts, the reactivity (polymerization activity) of Al-based catalysts is lower, and the reaction thereof is correspondingly milder, and by-products (diethylene glycol units: DEG) are less likely to be generated.

[0186] As a result, the regularity of PET is improved, and orientation is facilitated, thereby making it easy to express Re.

[0187] (1-3-1) Al-based catalysts

[0188] As the Al-based catalyst, the Al-based catalysts described in

[0013] to

[0148] of WO2011 / 040161 (

[0021] to

[0123] of US2012 / 0183761) can be used, and the contents described in these publications are incorporated into the present specification.

[0189] There is no particular limitation on the method for producing the polyester resin by polymerization using an Al-based catalyst. Specifically, polymerization can be carried out according to

[0091] to

[0094] of WO2012 / 008488 (

[0144] to

[0153] of US2013 / 0112271), and the contents described in these publications are incorporated into the present specification.

[0190] Furthermore, the Al-based catalyst can be prepared, for example, according to

[0052] to

[0054] ,

[0099] to

[0104] of JP-A-2012-122051 (

[0045] to

[0047] ,

[0091] to

[0096] of WO2012 / 029725), and the contents described in these publications are incorporated into the present specification.

[0191] The amount of the Al-based catalyst is preferably 3 to 80 ppm, more preferably 5 to 60 ppm, and even more preferably 5 to 40 ppm, as the amount of Al element relative to the mass of the polyester resin.

[0192] (1-3-2) Sb catalysts:

[0193] As the Sb-based catalyst, the Sb-based catalysts described in

[0050] and

[0052] to

[0054] of JP-A-2012-41519 can be used.

[0194] The method for polymerizing the polyester resin using the Sb-based catalyst is not particularly limited, and specifically, the polymerization can be carried out according to

[0086] to

[0087] of WO2012 / 157662.

[0195] (1-4) Additives:

[0196] It is also preferred to add known additives to the polyester film involved in this embodiment. Examples thereof include ultraviolet absorbers, particles, lubricants, anti-blocking agents, heat stabilizers, antioxidants, antistatic agents, light fastness agents, impact resistance improvers, lubricants, dyes, pigments, etc. Among them, polyester films generally require transparency, so it is preferred to limit the amount of additives added to a minimum.

[0197] (1-4-1) Ultraviolet (UV) absorber:

[0198] In order to prevent the liquid crystal of the liquid crystal display from being degraded by ultraviolet rays, the polyester film of this embodiment may contain an ultraviolet absorber. The ultraviolet absorber is a compound having ultraviolet absorption ability, and is not particularly limited as long as it can withstand the heat applied in the manufacturing process of the polyester film.

[0199] The ultraviolet absorber includes organic ultraviolet absorbers and inorganic ultraviolet absorbers, and organic ultraviolet absorbers are preferred from the viewpoint of transparency. The ultraviolet absorbers described in

[0057] of WO2012 / 157662 or cyclic imino ester ultraviolet absorbers described below can be used.

[0200] Examples of the cyclic iminoester ultraviolet absorber include, but are not limited to, 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, 2-phenyl-3,1-benzoxazin-4-one, 2-(1- or 2-naphthyl)-3,1-benzoxazin-4-one, 2-(4-biphenyl)-3,1-benzoxazin-4-one, 2-p-nitrophenyl-3,1-benzoxazin-4-one, 2-m-nitrophenyl-3,1-benzoxazin-4-one, 2-p-benzoylphenyl-3,1-benzoxazin-4-one, 2-p-methoxyphenyl-3,1-benzoxazin-4-one, 2-o-methoxyphenyl-3,1-benzoxazin-4-one, and 2-cyclohexyl-3,1-benzoxazin-4-one. , 1-benzoxazin-4-one, 2-p-(or m-)phthalimidephenyl-3,1-benzoxazin-4-one, N-phenyl-4-(3,1-benzoxazin-4-one-2-yl)phthalimide, N-benzoyl-4-(3,1-benzoxazin-4-one-2-yl)aniline, N-benzoyl-N-methyl-4-(3,1-benzoxazin-4-one-2-yl)aniline, 2-(p-(N-methylcarbonyl)phenyl)-3,1-benzoxazin-4-one, 2,2'-bis(3,1-benzoxazin-4-one), 2,2'-ethylenebis(3,1-benzoxazin-4-one), 2,2'-tetramethylenebis(3,1-benzoxazin-4-one), 2,2'-decamethylene Bis(3,1-benzoxazin-4-one), 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) [also referred to as 2,2'-p-phenylenebis(3,1-benzoxazin-4-one)], 2,2'-m-phenylenebis(3,1-benzoxazin-4-one), 2,2'-(4,4'-diphenylene)bis(3,1-benzoxazin-4-one), 2,2'-(2,6- or 1,5-naphthalene)bis(3,1-benzoxazin-4-one), 2,2'-(2-methyl-p-phenylene)bis(3,1-benzoxazin-4-one), 2,2'-(2-nitro-p-phenylene)bis(3,1-benzoxazin-4-one), 2,2'-(2-chloro-p-phenylene)bis(3,1-benzoxazin-4-one), 1-Benzoxazin-4-one), 2,2'-(1,4-cyclohexylene)bis(3,1-benzoxazin-4-one), 1,3,5-tri(3,1-benzoxazin-4-one-2-yl)benzene, 1,3,5-tri(3,1-benzoxazin-4-one-2-yl)naphthalene, 2,4,6-tri(3,1-benzoxazin-4-one-2-yl)naphthalene, 2,8-dimethyl-4H,6H-benzo(1,2-d;5,4-d')bis(1,3)-oxazine-4,6-dione, 2,7-dimethyl-4H,9H-benzo(1,2-d;4,5-d')bis(1,3)-oxazine-4,9-dione, 2,8-diphenyl-4H,8H-benzo(1,2-d;2,7-diphenyl-4H,9H-benzo(1,2-d; 4,5-d')bis(1,3)-oxazine-4,6-dione, 6,6'-bis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-bis(2-ethyl-4H,3,1-benzoxazine-4-one), 6,6'-bis(2-phenyl-4H,3,1-benzoxazine-4-one), 6,6'-methylenebis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-methylenebis(2-phenyl-4H,3,1-benzoxazine-4-one ), 6,6'-ethylenebis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-ethylenebis(2-phenyl-4H,3,1-benzoxazine-4-one), 6,6'-butylenebis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-butylenebis(2-phenyl-4H,3,1-benzoxazine-4-one), 6,6'-oxybis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-oxybis(2-phenyl-4H,3,1-benzoxazine-4-one), 6,6'-sulfonylbis(2-methyl-4H,3,1-benzoxazine-4 -ketone), 6,6'-sulfonylbis(2-phenyl-4H,3,1-benzoxazine-4-one), 6,6'-carbonylbis(2-methyl-4H,3,1-benzoxazine-4-one), 6,6'-carbonylbis(2-phenyl-4H,3,1-benzoxazine-4-one), 7,7'-methylenebis(2-methyl-4H,3,1-benzoxazine-4-one), 7,7'-methylenebis(2-phenyl-4H,3,1-benzoxazine-4-one), 7,7'-bis(2-methyl-4H,3,1-benzoxazine-4-one), 7,7'-ethylenebis(2-methyl-4H,3,1-benzoxazine-4-one 1-benzoxazine-4-one), 7,7'-oxybis(2-methyl-4H,3,1-benzoxazine-4-one), 7,7'-sulfonylbis(2-methyl-4H,3,1-benzoxazine-4-one), 7,7'-carbonylbis(2-methyl-4H,3,1-benzoxazine-4-one), 6,7'-bis(2-methyl-4H,3,1-benzoxazine-4-one), 6,7'-bis(2-phenyl-4H,3,1-benzoxazine-4-one, 6,7'-methylenebis(2-methyl-4H,3,1-benzoxazine-4-one), 6,7'-methylenebis(2-phenyl-4H,3,1-benzoxazine-4-one), etc.;

[0201] Among the above compounds, in consideration of color tone, benzoxazinone compounds which are less likely to yellow are preferably used, and for example, compounds represented by the following formula (6) are more preferably used.

[0202] Formula (6)

[0203] [Chemical formula 1]

[0204]

[0205] In the above formula (6), R represents a divalent aromatic hydrocarbon group, and X 1 and X 2 Each is independently selected from a hydrogen atom or the following functional groups, but is not necessarily limited thereto.

[0206] Functional group: alkyl, aryl, heteroaryl, halogen, alkoxy, aryloxy, hydroxyl, carboxyl, ester, nitro.

[0207] Among the compounds represented by the above formula (6), 2,2′-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) is particularly preferred.

[0208] The amount of the ultraviolet absorber that can be contained in the polyester film involved in this embodiment is usually 10.0% by mass or less, preferably in the range of 0.3 to 3.0% by mass, relative to the entire film. When the ultraviolet absorber is contained in an amount exceeding 10.0% by mass, the ultraviolet absorber bleeds out on the surface, which may lead to a decrease in surface functionality such as a decrease in adhesion.

[0209] Furthermore, when the polyester film involved in the present embodiment has a laminated structure, it is preferably at least a three-layer structure, and the ultraviolet light absorber is preferably blended into the middle layer (a layer other than the outermost layer). By blending the ultraviolet light absorber into the middle layer, it is possible to prevent the ultraviolet light absorber from seeping out to the film surface, and as a result, it is possible to maintain the properties such as the adhesion of the film.

[0210] The ultraviolet absorber can be blended by using, for example, the masterbatch method described in

[0050] to

[0051] of WO2011 / 162198.

[0211] (1-4-2) Other additives

[0212] The polyester film according to the present embodiment may contain other additives. For example, the additives described in

[0058] of WO2012 / 157662 may be used, and the contents described in the publication are incorporated into the present specification.

[0213] [Production method of polyester film]

[0214] A method for producing a polyester film, wherein the polyester film having a thickness of 40 to 500 μm is produced by using a transverse stretching device having a plurality of clamps, wherein the plurality of clamps respectively travel along a pair of rails provided on both sides of a film conveying path.

[0215] The manufacturing method comprises:

[0216] A preheating process, preheating the unstretched or longitudinally stretched polyester film at a heating rate of less than 600°C / min;

[0217] A transverse stretching step, in which the preheated polyester film is stretched in a direction perpendicular to the film conveying path while holding both edges of the film with a plurality of clamps, and the surface temperature of the polyester film (hereinafter sometimes referred to as "surface temperature") is gradually increased from the start of transverse stretching to the end of transverse stretching, the surface temperature at the start of transverse stretching is controlled to be 80° C. to 95° C., and the surface temperature at the end of transverse stretching is controlled to be 90° C. to 105° C., and the transverse stretching ratio is controlled to be within a range of 3.3 times to 4.8 times; and

[0218] In the heat setting step, the polyester film after the transverse stretching step is heated to the maximum temperature in the transverse stretching device to perform heat setting.

[0219] Here, the "unstretched polyester film" refers to a polyester film having a refractive index of 1.590 or less in both MD and TD. For example, a polyester film having a refractive index of 1.590 or less in both MD and TD even after slight stretching in MD is also included in the substantially unstretched polyester film.

[0220] Hereinafter, as a preferred embodiment of the method for producing the polyester film according to the present embodiment, a case where an unstretched polyester film is formed by melt extrusion and then stretched in the transverse direction to produce a uniaxially oriented polyester film will be described.

[0221] <Melt Kneading>

[0222] The unstretched polyester film is preferably formed into a film by melt-extruding a polyester resin.

[0223] The polyester resin or the masterbatch of the polyester resin and the additive produced by the above-mentioned masterbatch method is preferably dried to a moisture content of 200 ppm or less, and then introduced into a single-screw or twin-screw extruder to melt it. At this time, it is also preferred to melt it in nitrogen or in a vacuum in order to suppress the decomposition of the polyester resin. Detailed conditions can be referred to, for example,

[0051] to

[0052] of Japanese Patent Gazette No. 4962661 (

[0085] to

[0086] of US2013 / 0100378 Gazette) and implemented in accordance with these gazettes, and the contents described in these gazettes are introduced into the specification of this application. In addition, it is also preferred to use a gear pump to improve the delivery accuracy of the molten resin (melt). Furthermore, it is also preferred to use a filter with a pore size of 3μm to 20μm for removing foreign matter.

[0224] <Extrusion or coextrusion>

[0225] It is preferred that the melt containing the melt-kneaded polyester resin is extruded from a die, and it can be extruded in a single layer or in multiple layers (coextrusion). When extruded in multiple layers, for example, a layer containing an ultraviolet absorber (UV agent) and a layer not containing an ultraviolet absorber can be stacked, and a three-layer structure in which the layer containing the UV agent is set as the inner layer not only suppresses the degradation of the polarizer caused by ultraviolet rays, but also suppresses the seepage of the UV agent, and is therefore preferred.

[0226] The UV agent that seeps out is transferred to a roller that the film contacts during the film production process, and the friction coefficient between the film and the roller increases, which makes scratches more likely to occur, which is not preferable.

[0227] When the polyester film is manufactured by multi-layer extrusion, the thickness (ratio relative to the total layer) of the preferred inner layer (layer other than the outermost layer) of the obtained polyester film is preferably 50% or more and 95% or less, more preferably 60% or more and 90% or less, and further preferably 70% or more and 85% or less. Such lamination can be implemented by using a feed-block die or a multi-manifold die.

[0228] <Casting>

[0229] For example, it is preferred that, according to

[0059] of JP-A-2009-269301, a melt extruded from a die is extruded onto a casting drum and cooled and solidified to obtain an unstretched polyester film (roll film).

[0230] In the method for producing a polyester film according to the present embodiment, the refractive index of the unstretched polyester film in the longitudinal direction (MD) is preferably 1.590 or less, more preferably 1.585 or less, and even more preferably 1.580 or less.

[0231] In the method for producing the polyester film of the present embodiment, the crystallinity of the unstretched polyester film is preferably 5% or less, more preferably 3% or less, and further preferably 1% or less. In addition, the crystallinity of the unstretched polyester film referred to herein refers to the crystallinity of the central portion in the width direction (TD) of the film.

[0232] When adjusting the crystallinity, the temperature of the end of the casting drum may be lowered or air may be sent to the casting drum.

[0233] The crystallinity can be calculated from the density of the film. 3 ), density Y at 0% crystallinity = 1.335 g / cm 3 , density Z at 100% crystallinity = 1.501 g / cm 3The crystallinity (%) was derived by the following calculation formula.

[0234] Crystallinity = {Z × (XY)} / {X × (ZY)} × 100

[0235] In addition, the density was measured in accordance with JIS K7112.

[0236] <Formation of Polymer Layer>

[0237] The melt-extruded unstretched polyester film can be coated to form a polymer layer according to the purpose before or after stretching as described below.

[0238] The polymer layer generally includes a functional layer that a polarizing plate may have, and among these, an easy-adhesion layer is preferably formed. The easy-adhesion layer can be applied by the method described in

[0062] to

[0070] of WO2012 / 157662, for example.

[0239] <Warm-up>

[0240] Figure 3 An example of the structure of a transverse stretching device used in the transverse stretching step is schematically shown.

[0241] As a preheating step before the start of stretching in the transverse stretching step, it is preferred to preheat the unstretched polyester film at a heating rate of 600°C / min or less. If the heating rate of the film before the start of stretching in the transverse stretching step is 600°C / min or less, the film is stretched in a state where the molecular chains start to move sufficiently, and the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively increasing.

[0242] From this viewpoint, the heating rate in the preheating step is more preferably 500° C. / min or less, and further preferably 400° C. / min or less.

[0243] The temperature increase rate in the preheating step may be 40° C. / min to 600° C. / min, 40° C. / min to 500° C. / min, or 40° C. / min to 400° C. / min.

[0244] <Horizontal stretching>

[0245] In the transverse stretching process, Figure 3 As shown, a transverse stretching device (also called a "tenter-type stretching device" or "tenter") having a plurality of clamps 20 is used to perform transverse stretching in a state where both edges of the unstretched polyester film are respectively held by the clamps 20, and the clamps 20 travel along a pair of rails provided on both sides of the film conveying path. In addition, the unstretched polyester film may be held by the clamps from the stage of the preheating process.

[0246] There is no particular limitation on the stretching device having the clamp 20 that travels along a pair of tracks provided on both sides of the film conveying path. The pair of tracks generally uses a pair of ring-shaped tracks. In addition, the meaning of the clamp is the same as the gripping member.

[0247] The unstretched polyester film is stretched transversely. The unstretched polyester film is stretched transversely in a direction (TD) perpendicular to the film conveying direction (MD) while being conveyed along the film conveying path. That is, transverse stretching can be achieved by holding both ends of the film with clamps and expanding the width between the clamps while heating.

[0248] By performing transverse stretching, the delay Re in the in-plane direction can be made to be larger. In particular, in order to achieve a polyester film that satisfies the preferred range of Re and Re / Rth, it is preferred to perform at least transverse stretching. In addition, longitudinal stretching can also be performed before the preheating process or before the transverse stretching process.

[0249] The surface temperature at the start of stretching in the transverse stretching step is preferably 80°C to 95°C, more preferably 82°C to 93°C, and further preferably 84°C to 92°C.

[0250] If the surface temperature at the start of stretching in the transverse stretching process is 80°C or higher, orientation and orientation crystallization will not proceed excessively during the stretching stage, and excessive increases in shear plane perpendicular stress and shear plane yield stress can be suppressed. In addition, the increase in Rth can be suppressed, and the Re / Rth ratio becomes 0.6 or higher, thereby suppressing visual recognition of rainbow-like unevenness.

[0251] If the surface temperature at the start of stretching in the transverse stretching step is 95°C or less, the growth of spherulites due to insufficient orientation can be suppressed, and excessive decreases in shear plane perpendicular stress and shear plane yield stress and film whitening can be suppressed, and Re can be easily increased sufficiently.

[0252] In the method for producing a polyester film according to the present embodiment, the surface temperature at the end of stretching in the transverse stretching step is preferably 90°C to 105°C, more preferably 92°C to 102°C, and further preferably 93°C to 100°C.

[0253] If the surface temperature at the end of the stretching in the transverse stretching process is 90°C or higher, the orientation and orientation crystallization will not be excessively advanced during the stretching stage, and the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively increasing. In addition, the increase in Rth can be suppressed, and the Re / Rth ratio becomes 0.6 or higher, thereby suppressing the visual recognition of rainbow-like unevenness.

[0254] If the surface temperature at the end of stretching in the transverse stretching process is below 105°C, the growth of spherulites caused by insufficient orientation can be suppressed, and the excessive decrease in the shear plane perpendicular stress and the shear plane yield stress and the whitening of the film can be suppressed, and Re, which affects the suppression of rainbow-like unevenness, can be easily increased.

[0255] The surface temperature is gradually increased from the start of stretching to the end of stretching in the transverse stretching step. Here, "gradually increased" may be a continuous increase or a stepwise increase.

[0256] The difference in surface temperature between the time when stretching is completed and the time when stretching is started is preferably 1° C. or more, more preferably 3° C. or more, and most preferably 5° C. or more.

[0257] If the surface temperature is gradually increased from the start to the end of stretching, spherulites are less likely to form, excessive orientation can be suppressed, Re and Re / Rth can be easily adjusted to be within the preferred ranges, and rainbow-like unevenness is less likely to be visually discernible.

[0258] The transverse stretching ratio in the transverse stretching step is preferably controlled within the range of 3.3 to 4.8, more preferably 3.5 to 4.5, and further preferably 3.7 to 4.3.

[0259] If the transverse stretching ratio is 3.3 times or more, the shear plane perpendicular stress and shear plane yield stress of the film can be suppressed from excessively decreasing, and the reduction of Re which is effective in suppressing rainbow unevenness can be suppressed. If the transverse stretching ratio is 4.8 times or less, the shear plane perpendicular stress and shear plane yield stress of the film can be suppressed from excessively increasing and becoming brittle.

[0260] In the transverse stretching step, the surface temperature when the transverse stretching ratio is in the range of 1 to less than 2 is preferably 80°C to 92°C, more preferably 82°C to 91°C, and further preferably 84°C to 91°C.

[0261] If the surface temperature is 80°C or higher when the transverse stretching ratio in the transverse stretching process is in the range of 1 or more and less than 2 times, the orientation and orientation crystallization will not be excessively carried out in the stretching stage, and the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively increasing. In addition, the increase of Rth can be suppressed, and the Re / Rth ratio becomes 0.6 or more, and the visual recognition of rainbow-like unevenness can be suppressed.

[0262] If the surface temperature is below 92°C when the lateral stretching ratio in the lateral stretching process is in the range of more than 1 times and less than 2 times, the growth of spherulites caused by insufficient orientation can be suppressed, and the excessive decrease in the shear plane perpendicular stress and the shear plane yield stress, as well as the insufficient increase in Re, which leads to visual recognition of rainbow-like unevenness, can be suppressed.

[0263] In the transverse stretching step, the surface temperature when the transverse stretching ratio is in the range of 2 to less than 3 times is preferably 85 to 97°C, more preferably 86 to 97°C, and further preferably 87 to 96°C.

[0264] In the transverse stretching process, if the surface temperature is 85°C or higher when the transverse stretching ratio is in the range of 2 or more and less than 3 times, the orientation and orientation crystallization will not be excessively carried out in the stretching stage, and the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively increasing. In addition, the increase of Rth can be suppressed, and the Re / Rth ratio becomes 0.6 or less, and the visual recognition of rainbow-like unevenness can be suppressed.

[0265] In the transverse stretching process, if the surface temperature is 97°C or less when the transverse stretching ratio is in the range of 2 or more and less than 3 times, the growth of spherulites caused by insufficient orientation can be suppressed, and the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively decreasing. In addition, Re, which is effective in suppressing rainbow unevenness, is sufficiently increased, and the rainbow unevenness can be suppressed from being visually recognized.

[0266] In the transverse stretching step, the surface temperature when the transverse stretching ratio is 3 times or more is preferably 90°C to 102°C, more preferably 92°C to 101°C, and further preferably 93°C to 100°C.

[0267] In the transverse stretching process, if the surface temperature is 90°C or higher when the transverse stretching ratio is 3 times or higher, the orientation and orientation crystallization will not be excessively carried out in the stretching stage, and the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively increasing. In addition, the increase of Rth can be suppressed, and the Re / Rth ratio becomes 0.6 or higher, which can suppress the rainbow unevenness from being visually recognized.

[0268] In the transverse stretching process, if the surface temperature is 102°C or less when the transverse stretching ratio is 3 times or more, the growth of spherulites caused by insufficient orientation can be suppressed, and the shear plane perpendicular stress and shear plane yield stress can be suppressed from excessively decreasing. In addition, Re is sufficiently increased, and the visual recognition of rainbow-like unevenness can be suppressed.

[0269] In addition, since the surface temperature is gradually increased from the start of stretching to the end of stretching, in the transverse stretching process, the surface temperature when the transverse stretching ratio is in the range of 1 or more and less than 2 times, the surface temperature when the transverse stretching ratio is in the range of 2 or more and less than 3 times, and the surface temperature when the transverse stretching ratio is in the range of 3 or more times will not be lower than the surface temperature in the range of stretching with a small transverse stretching ratio. That is, the surface temperature when the transverse stretching ratio is in the range of 2 or more and less than 3 times will not be lower than the surface temperature when the transverse stretching ratio is in the range of 1 or more and less than 2 times, and the surface temperature when the transverse stretching ratio is in the range of 3 or more times will not be lower than the surface temperature when the transverse stretching ratio is in the range of 2 or more and less than 3 times.

[0270] In the transverse stretching step, the rate of increase in the surface temperature during stretching is preferably set to 60° C. / min or less, more preferably 50° C. / min or less, and even more preferably 40° C. / min or less.

[0271] In the transverse stretching process, if the temperature rise rate of the surface temperature during stretching is 60°C / min or less, the rapid movement of the molecular chain during stretching can be suppressed, and the shear plane vertical stress and the shear plane yield stress can be suppressed from excessively decreasing. In addition, the Re that is effective in suppressing the rainbow unevenness rises sufficiently, and the rainbow unevenness is not easily visually recognized.

[0272] In the transverse stretching step, the rate of increase in the surface temperature during stretching may be 5°C / min to 60°C / min, 5°C / min to 50°C / min, or 5°C / min to 40°C / min.

[0273] <Heat setting>

[0274] The method comprises a heat setting step in which the polyester film stretched transversely is heated to a maximum temperature in a transverse stretching device to perform heat setting.

[0275] After stretching, a heat treatment called "heat setting" is performed to promote crystallization. By performing this heat treatment at a temperature exceeding the stretching temperature, crystallization is promoted, thereby increasing the strength of the film.

[0276] During heat setting, the volume shrinks due to crystallization.

[0277] As a method of heat setting, it can be achieved by providing a plurality of slits parallel to the width direction for sending hot air to the stretching section and setting the temperature of the gas blown from the slits to be higher than the temperature of the stretching section.

[0278] Furthermore, a heat source (IR heater, halogen heater, etc.) may be provided near the stretching (section) exit to increase the temperature.

[0279] The highest surface temperature of the polyester film in the heat setting step is preferably 130°C to 230°C, more preferably 150°C to 210°C, and further preferably 160 to 200°C.

[0280] If the highest surface temperature in the heat setting process is 130° C. or higher, the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively decreasing, and if it is 230° C. or lower, the shear plane perpendicular stress and the shear plane yield stress can be suppressed from excessively increasing.

[0281] The rate of increase in the surface temperature of the film from the end of the transverse stretching step to the maximum temperature in the heat setting step is preferably 1000° C. / min or less, more preferably 800° C. / min or less, and even more preferably 700° C. / min or less.

[0282] Here, the “maximum temperature in the heat setting step” refers to the highest point of the surface temperature reached by the film in the heat setting region, and can be obtained by measuring the surface temperature (film surface temperature) of the film in the heat setting region with a radiation thermometer.

[0283] If the heating rate of the film from the end of the transverse stretching process to the heat setting process is below 1000°C / min, the rapid relaxation of molecules before crystallization can be suppressed, and the excessive decrease in the shear plane perpendicular stress and the shear plane yield stress, or the insufficient increase in Re that causes rainbow-like unevenness to be visually recognized can be suppressed.

[0284] The rate of increase in the surface temperature of the film from the end of the transverse stretching step to the maximum temperature in the heat setting step may be 50°C / min to 1000°C / min, 50°C / min to 800°C / min, or 50°C / min to 700°C / min.

[0285] The time during which the surface temperature exceeds 130° C. is preferably 180 seconds or less, more preferably 120 seconds or less, and further preferably 60 seconds or less.

[0286] When the time during which the surface temperature exceeds 130° C. is 180 seconds or less, crystallization does not proceed excessively, and excessive increases in the shear plane perpendicular stress and the shear plane yield stress, or excessive increases in Rth that cause rainbow unevenness to be visually recognized, can be suppressed.

[0287] The time during which the surface temperature exceeds 130° C. may be 10 seconds to 180 seconds, 10 seconds to 120 seconds, or 10 seconds to 60 seconds.

[0288] <Heat relaxation>

[0289] It is preferable to include a heat relaxation step in which the polyester film after the heat setting step is heated and the length of at least the transverse direction (TD) of the polyester film is reduced. In other words, it is preferable to include: a heat setting step in which the transversely stretched polyester film is heated to the highest temperature in the transverse stretching device; and a heat relaxation step in which the distance between the pair of rails is reduced while the polyester film after the heat setting step is heated before the transversely stretched polyester film is released from the clamp.

[0290] In addition, the heat relaxation process is not strictly limited to being performed after the heat setting process, and the heat setting process and the heat relaxation process may be performed simultaneously. When the heat setting process and the heat relaxation process are performed simultaneously, it is preferred that the heat setting process be performed until the point when the heating reaches the highest temperature in the transverse stretching device, and the heat relaxation is continued at a temperature not exceeding the highest temperature in the transverse stretching device.

[0291] After the heat setting step, it is preferred that the film be relaxed (shrinked) while being heat treated, preferably in at least one of TD (transverse direction) and MD (machine direction).

[0292] Transverse relaxation can be achieved by reducing the width of the widened clamp.

[0293] Such relaxation can be achieved, for example, by using a pantograph-shaped chuck in the tenter and reducing the interval between the pantographs, or by driving the chuck on an electromagnet and reducing its speed.

[0294] In the heat relaxation process, from the viewpoint of suppressing scratches on the polyester film, the ratio of the length of the MD of the heat-set polyester film to be reduced, i.e., the relaxation rate of the MD, is preferably set to 1 to 7%, more preferably 2 to 6%, and further preferably 3 to 5%. If the relaxation rate of the MD is 1% or more, the heat shrinkage rate of the MD can be reduced, and wrinkles are less likely to occur. If the relaxation rate of the MD is 7% or less, it is less likely to cause relaxation in the MD during the relaxation process, and it is less likely to cause surface damage, so it is preferred.

[0295] From the viewpoint of suppressing scratches on the polyester film, the ratio of the length of the TD of the heat-set polyester film to be reduced, i.e., the relaxation rate of the TD, is preferably set to 0 to 6%, more preferably 1 to 4%, and further preferably 1 to 3%. If the relaxation rate of the TD is 6% or less, relaxation is less likely to occur in the TD during the relaxation process, and it is less likely to cause a planar defect, so it is preferred.

[0296] The relaxation temperature in TD (transverse direction) is preferably within the range of the above-mentioned heat setting temperature. As long as the polyester film after transverse stretching can be heated to the highest temperature in the transverse stretching device for heat setting, it can be the same temperature as the heat setting temperature (i.e., it can reach the highest temperature in the transverse stretching device), or it can also be a temperature lower than the heat setting temperature.

[0297] By performing the above-mentioned preheating step, transverse stretching step, heat setting step, and further performing a heat relaxation step as required, it is easy to achieve Re, Rth, and Re / Rth of the polyester film involved in this embodiment, thereby making it easy to manufacture the polyester film involved in this embodiment that shows the rainbow unevenness reduction effect.

[0298] <Cooling>

[0299] Before releasing the heat-set or heat-relaxed polyester film from the jig, it is preferred to include a step of cooling the polyester film. From the viewpoint of easily lowering the temperature of the jig when releasing the polyester film from the jig, it is preferred to cool the heat-set or heat-relaxed polyester film before releasing it from the jig.

[0300] The cooling temperature of the polyester film after heat setting or heat relaxation is preferably 80° C. or lower, more preferably 70° C. or lower, and particularly preferably 60° C. or lower.

[0301] As a method of cooling the polyester film after heat setting, a method of blowing cold air to the polyester film is specifically mentioned.

[0302] In addition, during the preheating, stretching, heat setting, heat relaxation and cooling in the present embodiment, as a temperature control mechanism for heating or cooling the polyester film, blowing warm air or cold air to the polyester film, or making the polyester film contact with the surface of a metal plate that can control the temperature or passing near the metal plate can be cited.

[0303] <Release Film from the Clamp>

[0304] After the above steps, the polyester film is released from the jig.

[0305] The surface temperature of the polyester film when it is released from the jig is preferably controlled within a range of 40 to 140° C. The surface temperature of the polyester film when it is released from the gripping member is more preferably 50° C. to 120° C., and even more preferably 60° C. to 100° C.

[0306] In the method for manufacturing the polyester film according to the present embodiment, the thickness of the polyester film after film formation (after the process of releasing from the clamp) is 40 μm or more and 500 μm or less, more preferably 60 μm or more and 400 μm or less, and further preferably 80 μm or more and 300 μm or less. The reason why the thickness of the polyester film is preferably set within the above range is the same as the reason for the film thickness of the polyester film according to the present embodiment.

[0307] <Film recovery, cutting and winding>

[0308] After release from the clamps, the film is trimmed, cut, thickness processed as required and reeled up for recycling.

[0309] In the method for manufacturing the polyester film according to the present embodiment, from the viewpoint of effectively ensuring the width of the film product and preventing the device from being too large in size, the width of the film after being released from the clamp is preferably 0.8 to 6 m, more preferably 1 to 5 m, and particularly preferably 1 to 4 m. Optical films requiring precision are usually made with a width of less than 3 m, and in the present embodiment, the film is preferably made with the width as described above.

[0310] Furthermore, the wide film may be cut into preferably 2 or more and 6 or less, more preferably 2 or more and 5 or less, and further preferably 3 or more and 4 or less, and then wound up.

[0311] It is preferred to perform thickness processing (giving knurling) on ​​both ends after cutting.

[0312] Preferably, the film is wound around a core having a diameter of 70 mm to 600 mm for a length of 1,000 to 10,000 m. The winding tension per unit cross-sectional area of ​​the film is preferably 3 to 30 kgf / cm 2 , more preferably 5 to 25 kgf / cm 2 , more preferably 7 to 20 kgf / cm 2 Furthermore, it is also preferred to attach a masking film before winding.

[0313] [Hard Coat]

[0314] The polyester film according to the present embodiment can be preferably used as a base film of a hard coat film.

[0315] That is, the hard coat film according to the present embodiment includes: a base film including the polyester film according to the present embodiment; and a hard coat layer laminated on at least one surface of the polyester film.

[0316] <Hard Coating>

[0317] Hereinafter, the hard coat layer of the hard coat film according to the present embodiment will be described.

[0318] The hard coat layer may be formed by any coating method of a wet coating method or a dry coating method (vacuum film formation), but is preferably formed by a wet coating method having excellent productivity.

[0319] As the hard coat layer, for example, Japanese Patent Application Laid-Open No. 2013-45045, Japanese Patent Application Laid-Open No. 2013-43352, Japanese Patent Application Laid-Open No. 2012-232459, Japanese Patent Application Laid-Open No. 2012-128157, Japanese Patent Application Laid-Open No. 2011-131409, Japanese Patent Application Laid-Open No. 2011-131404, Japanese Patent Application Laid-Open No. 2011-126162, Japanese Patent Application Laid-Open No. 2011-75705, Japanese Patent Application Laid-Open No. 2009-286981 ... The hard coating layers are described in Japanese Unexamined Patent Application Publication No. 2009-263567, Japanese Unexamined Patent Application Publication No. 2009-75248, Japanese Unexamined Patent Application Publication No. 2007-164206, Japanese Unexamined Patent Application Publication No. 2006-96811, Japanese Unexamined Patent Application Publication No. 2004-75970, Japanese Unexamined Patent Application Publication No. 2002-156505, Japanese Unexamined Patent Application Publication No. 2001-272503, WO12 / 018087, WO12 / 098967, WO12 / 086659, and WO11 / 105594.

[0320] (Thickness of hard coating)

[0321] The hard coating film according to the present embodiment preferably has a thickness of 5 μm or more. When the thickness of the hard coating layer is 5 μm or more, a hard coating film having high scratch resistance can be obtained.

[0322] From this viewpoint, the thickness of the hard coat layer of the hard coat film according to the present embodiment is more preferably 10 μm or more, and further preferably 15 μm or more.

[0323] If the thickness of the hard coat layer is too thick, punching tends to be difficult, so the thickness of the hard coat layer is preferably 40 μm or less, more preferably 35 μm or less.

[0324] (Constitutional materials of hard coat layer)

[0325] The hard coat layer of the hard coat film according to the present embodiment includes at least a structure derived from the following a), a structure derived from the following b), the following c), and the following d).

[0326] When the total solid content of the hard coat layer is 100 mass %, the hard coat layer preferably contains 15 to 70 mass % of a structure derived from the following a), 25 to 80 mass % of a structure derived from the following b), 0.1 to 10 mass % of the following c), and 0.1 to 10 mass % of the following d).

[0327] a) A compound having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less

[0328] b) A compound having three or more groups containing ethylenically unsaturated double bonds in the molecule

[0329] c) Free Radical Polymerization Initiator

[0330] d) Cationic polymerization initiator

[0331] By providing a hard coat layer having such a structure, the hard coat film according to the present embodiment has a high pencil hardness, is excellent in smoothness, and can suppress changes in film appearance after aging under wet heat.

[0332] In this embodiment, the hard coat layer preferably has hard coat properties. In this specification, hard coat properties refer to a pencil hardness of 7H or higher from the perspective of using the hard coat film as the outermost protective film of an image display device instead of glass. The hard coat layer preferably has a pencil hardness of 8H or higher.

[0333] The hard coating film according to the present embodiment having such a structure is preferably produced by a method for producing a hard coating film according to the present embodiment described below.

[0334] <Structure>

[0335] The hard coating film involved in this embodiment is preferably a structure in which a hard coating layer is applied on at least one surface of the polyester film involved in the above-mentioned embodiment. The hard coating film involved in this embodiment is formed by curing a hard coating layer forming composition containing a), b), c) and d), and when the total solid content of the hard coating layer forming composition is set to 100% by mass, it is more preferred that the hard coating layer forming composition contains 15 to 70% by mass of a), 25 to 80% by mass of b), 0.1 to 10% by mass of c), and 0.1 to 10% by mass of d).

[0336] <Hard Coat Layer and Hard Coat Layer-Forming Composition>

[0337] Hereinafter, details of each component contained in the hard coat layer and the hard coat layer-forming composition will be described.

[0338] [a) a compound having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less]

[0339] In the hard coating film according to the present embodiment, when the total solid content of the hard coating layer is 100% by mass, the hard coating layer contains 15 to 70% by mass of a structure derived from the following a).

[0340] a) A compound having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less.

[0341] Furthermore, the hard coat layer is formed by curing a hard coat layer forming composition comprising at least a), b), c) and d), and when the total solid content of the hard coat layer forming composition is set to 100% by mass, the hard coat layer forming composition preferably contains 15 to 70% by mass of a).

[0342] The compound a) having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less contained in the hard coat layer forming composition is described. The compound a) having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less is also referred to as "component a)".

[0343] As the group containing an ethylenically unsaturated double bond, there can be mentioned polymerizable functional groups such as (meth)acryloyl, vinyl, styryl, and allyl, among which (meth)acryloyl and -C(O)OCH=CH2 are preferred, and (meth)acryloyl is particularly preferred. By having a group containing an ethylenically unsaturated double bond, high hardness can be maintained and moisture-heat resistance can be imparted.

[0344] In addition, in this specification, "(meth)acryl" means a meaning including "acryl" and "methacryl", "(meth)acrylate" means a meaning including "acrylate" and "methacrylate", and "(meth)acrylic acid" means a meaning including "acrylic acid" and "methacrylic acid".

[0345] In the present embodiment, the number of epoxy groups and groups containing ethylenically unsaturated double bonds in the molecule is 1. This is because when the number of each functional group is 1, compared with the case where the number of each functional group is 2 or more, the number of functional groups (epoxy groups and groups containing ethylenically unsaturated double bonds) is reduced, the molecular weight is reduced, and the pencil hardness is improved.

[0346] The molecular weight of the component a) is 300 or less, preferably 210 or less, and more preferably 200 or less.

[0347] By setting the molecular weight of the component a) to 300 or less, the number of sites other than the epoxy group and the group containing an ethylenically unsaturated double bond can be reduced, and the pencil hardness can be increased.

[0348] Furthermore, from the viewpoint of suppressing volatilization during formation of the hard coat layer, the molecular weight of the component a) is preferably 100 or more, and more preferably 150 or more.

[0349] The component a) is not particularly limited as long as it has one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and has a molecular weight of 300 or less, but is preferably a compound represented by the following formula (7).

[0350] Formula (7)

[0351] [Chemical formula 2]

[0352]

[0353] In formula (7), R represents a monocyclic hydrocarbon or a crosslinked hydrocarbon, L represents a single bond or a divalent linking group, and Q represents a group containing an ethylenically unsaturated double bond.

[0354] When R in formula (7) is a monocyclic hydrocarbon, it is preferably an alicyclic hydrocarbon, more preferably an alicyclic group having 4 to 10 carbon atoms, further preferably an alicyclic group having 5 to 7 carbon atoms, and particularly preferably an alicyclic group having 6 carbon atoms. Specifically, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl are preferred, and cyclohexyl is particularly preferred.

[0355] When R in formula (7) is a cross-linked hydrocarbon, preferably a 2-ring cross-linked (bicyclic) or 3-ring cross-linked (tricyclic) hydrocarbon, examples of which include cross-linked hydrocarbons having 5 to 20 carbon atoms, including norbornyl, bornyl, isobornyl, tricyclodecyl, dicyclopentenyl, dicyclopentanyl, tricyclopentenyl and tricyclopentanyl, adamantyl, lower alkyl substituted adamantyl, and the like.

[0356] When L represents a divalent linking group, a divalent aliphatic hydrocarbon group is preferred. The divalent aliphatic hydrocarbon group preferably has 1 to 6 carbon atoms, more preferably 1 to 3, and further preferably 1. The divalent aliphatic hydrocarbon group is preferably a linear, branched, or cyclic alkylene group, more preferably a linear or branched alkylene group, and further preferably a linear alkylene group.

[0357] Examples of Q include polymerizable functional groups such as a (meth)acryloyl group, a vinyl group, a styryl group, and an allyl group. Among them, a (meth)acryloyl group and -C(O)OCH=CH2 are preferred, and a (meth)acryloyl group is particularly preferred.

[0358] The specific compound of the component a) is not particularly limited as long as it has one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and has a molecular weight of 300 or less. The compounds described in paragraph

[0015] of Japanese Patent Application Laid-Open No. 10-17614, the compounds represented by the following formula (1A) or (1B), 1,2-epoxy-4-vinylcyclohexane, etc. can be used.

[0359] Among them, the compound represented by the following formula (1A) or (1B) is more preferred, and the compound represented by the following formula (1A) having a low molecular weight is further preferred. In addition, the compound represented by the following formula (1A) is also preferably an isomer thereof. In the following formula (1A), L2 represents a divalent aliphatic hydrocarbon group having 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and from the viewpoint of improving smoothness, more preferably 1 carbon atom (i.e., component a) is (meth) acrylate epoxycyclohexylmethyl ester).

[0360] By using these compounds, it is possible to achieve both high pencil hardness and excellent smoothness at a higher level.

[0361] [Chemical formula 3]

[0362]

[0363] In the formula (1A), R1 represents a hydrogen atom or a methyl group, and L2 represents a divalent aliphatic hydrocarbon group having 1 to 6 carbon atoms.

[0364] [Chemical formula 4]

[0365]

[0366] In the formula (1B), R1 represents a hydrogen atom or a methyl group, and L2 represents a divalent aliphatic hydrocarbon group having 1 to 6 carbon atoms.

[0367] The divalent aliphatic hydrocarbon group of L2 in formula (1A) and (1B) has 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and even more preferably 1 carbon atom. The divalent aliphatic hydrocarbon group is preferably a linear, branched or cyclic alkylene group, more preferably a linear or branched alkylene group, and even more preferably a linear alkylene group.

[0368] When the total solid content of the hard coat layer is set to 100% by mass, it contains 15 to 70% by mass of the structure derived from a). When the total solid content of the hard coat layer forming composition in the present embodiment is set to 100% by mass, it contains 15 to 70% by mass of component a). If the content of the structure derived from a) or the component a) relative to the hard coat layer or the hard coat layer forming composition is 15% by mass or more, the surface smoothness is fully improved. On the other hand, when the content of the structure derived from a) or the component a) relative to the hard coat layer or the hard coat layer forming composition is 70% by mass or less, the surface hardness can be fully improved.

[0369] When the total solid content of the hard coat layer is 100% by mass, it is preferred that 18 to 50% by mass of the structure derived from a) is contained, and more preferably 22 to 40% by mass. When the total solid content of the hard coat layer forming composition in the present embodiment is 100% by mass, it is preferred that 18 to 50% by mass of the component a) is contained, and more preferably 22 to 40% by mass.

[0370] [b) a compound having three or more groups containing ethylenically unsaturated double bonds in the molecule]

[0371] In the hard coating film according to the present embodiment, when the total solid content of the hard coating layer is 100% by mass, the hard coating layer contains 25 to 80% by mass of a structure derived from the following b).

[0372] b) A compound having three or more groups containing an ethylenically unsaturated double bond in the molecule.

[0373] Furthermore, the hard coat layer is formed by curing a hard coat layer forming composition comprising at least a), b), c) and d), and when the total solid content of the hard coat layer forming composition is set to 100% by mass, the hard coat layer forming composition preferably contains 25 to 80% by mass of b).

[0374] b) a compound having three or more groups containing ethylenically unsaturated double bonds in a molecule contained in the hard coat-forming composition of the present embodiment is described. b) a compound having three or more groups containing ethylenically unsaturated double bonds in a molecule is also referred to as "component b)".

[0375] The component b) can express high hardness by having three or more groups containing ethylenically unsaturated double bonds in the molecule.

[0376] The component b) may have 3 or more and 20 or less groups containing ethylenically unsaturated double bonds in the molecule.

[0377] As component b), esters of polyols and (meth) acrylic acid, vinylbenzene and its derivatives, vinyl sulfone, (meth) acrylamide, etc. can be cited. Among them, from the viewpoint of hardness, compounds having three or more (meth) acryloyl groups are preferred, and examples thereof include acrylate compounds that form cured products with high hardness, which are widely used in the industry. As such compounds, compounds having three or more groups containing ethylenically unsaturated double bonds in the molecule, which are esters of polyols and (meth) acrylic acid, can be cited. For example, (di)pentaerythritol tetra(meth)acrylate, (di)pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, EO-modified phosphoric acid tri(meth)acrylate, trimethylolethane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, (di)pentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, pentaerythritol hexa(meth)acrylate, 1,2,3-cyclohexane tetramethacrylate, polyurethane polyacrylate, polyester polyacrylate, caprolactone-modified tri(acryloyloxyethyl)isocyanurate, tripentaerythritol triacrylate, tripentaerythritol hexatriacrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol triacrylate, and the like can be mentioned.

[0378] Also preferred are resins (oligomers or prepolymers) having three or more (meth)acryloyl groups, polyfunctional (meth)acrylates having three or more (meth)acryloyl groups, and urethane (meth)acrylates.

[0379] Examples of the resin (oligomer or prepolymer) having three or more (meth)acryloyl groups include polyester resins, polyether resins, acrylic resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, oligomers or prepolymers of polyfunctional compounds such as polyols, and the like.

[0380] Specific examples of the polyfunctional (meth)acrylate having three or more (meth)acryloyl groups include the exemplary compounds described in paragraph 0096 of JP-A-2007-256844.

[0381] Specific examples of the polyfunctional acrylate compounds having three or more (meth)acryloyl groups include esters of polyols and (meth)acrylic acid, such as KAYARAD DPHA, DPHA-2C, PET-30, TMPTA, TPA-320, TPA-330, RP-1040, T-1420, D-310, DPCA-20, DPCA-30, DPCA-60, GPO-303 manufactured by Nippon Kayaku Co., Ltd., and V#400 and V#36095D manufactured by Osaka Organic Chemical Industry Co., Ltd. In addition, violet light UV-1400B, UV-1700B, UV-6300B, UV-7550B, UV-7600B, UV-7605B, UV-7610B, UV-7620EA, UV-7630B, UV-7640B, UV-6630B, UV-7000B, UV-7510B, UV-7461TE, UV-3000B, UV-3200B, UV-3210EA, UV-3310EA, UV-3310B, UV-3500BA, UV-3520TL, UV-3700B, UV-6100B, UV-6640B, UV-2000B, UV-2010B, UV-2250EA, UV-2750B (The Nippon Synthetic Chemical Industry Co., Ltd.), UL-503LN (manufactured by Kyoeisha Chemical Co., Ltd.), UNIDIC 17-806, 17-813, V-4030, V-4000BA (manufactured by DIC Corporation), EB-1290K, EB-220, EB-5129, EB-1830, EB-4358 (manufactured by Daicel-UCB Co., Ltd.), Haikopu AU-2010, AU-2020 (manufactured by TOKUSHIKI CO., Ltd.), ARONIX M-1960 (manufactured by TOAGOSEI CO., LTD.), Art Resin UN-3320HA, UN-3320HC, UN-3320HS, UN-904, HDP-4T and other trifunctional or higher urethane acrylate compounds, ARONIX Trifunctional or higher-functional polyester compounds such as M-8100, M-8030, M-9050 (manufactured by TOAGOSEI CO., LTD.) and KBM-8307 (manufactured by DAICEL-ALLNEXL T.).

[0382] Furthermore, the component b) may be composed of a single compound or a plurality of compounds may be used in combination.

[0383] When the total solid content of the hard coat layer is 100% by mass, the structure derived from b) is contained in an amount of 25 to 80% by mass.

[0384] When the total solid content of the hard coat forming composition in the present embodiment is set to 100% by mass, 25 to 80% by mass of component b) is contained. If the content of the structure derived from b) or the component b) relative to the hard coat or the hard coat forming composition is 25% by mass or more, sufficient hardness can be obtained. On the other hand, when the content of the structure derived from b) or the component b) relative to the hard coat or the hard coat forming composition is 80% by mass or less, the content of the structure derived from a) or the component a) is reduced, so the smoothness is sufficient.

[0385] When the total solid content of the hard coat layer is 100% by mass, it is preferred that 40 to 75% by mass of the structure derived from b) is contained, and more preferably 60 to 75% by mass. When the total solid content of the hard coat layer forming composition in the present embodiment is 100% by mass, it is preferred that 40 to 75% by mass of the component b) is contained, and more preferably 60 to 75% by mass.

[0386] [Other curable compounds]

[0387] The hard coat forming composition may include other curable compounds (hereinafter, also referred to as "other curable compounds") other than component a) and component b). As other curable compounds, various compounds having polymerizable groups that can be cured (polymerized) by curing treatment can be used. As polymerizable groups, polymerizable groups that can be polymerized by irradiation with light, electron beams or radiation, polymerizable groups that can be polymerized by heating, preferably photopolymerizable groups, can be cited. In addition, other curable compounds can be monomers, oligomers, prepolymers, etc.

[0388] Specific examples of the polymerizable group include polymerizable unsaturated groups such as (meth)acryloyl, vinyl, styryl, and allyl, and ring-opening polymerizable groups such as epoxy. Among them, (meth)acryloyl is preferred from the viewpoint of curability.

[0389] Specific examples of other curable compounds that may be contained in the hard coat layer-forming composition include the following compounds.

[0390] (Meth)acrylic acid diesters of alkylene glycols such as neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, and propylene glycol di(meth)acrylate; (meth)acrylic acid diesters of polyoxyalkylene glycols such as triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; (meth)acrylic acid diesters of polyols such as pentaerythritol di(meth)acrylate; (meth)acrylic acid diesters of ethylene oxide or propylene oxide adducts such as 2,2-bis{4-(acryloxydiethoxy)phenyl}propane and 2,2-bis{4-(acryloxypolypropoxy)phenyl}propane; urethane (meth)acrylates; polyester (meth)acrylates; isocyanuric acid acrylates; epoxy (meth)acrylates.

[0391] As the urethane (meth) acrylate, for example, urethane (meth) acrylates can be exemplified by reacting hydroxyl-containing compounds such as alcohols, polyols and / or hydroxyl-containing acrylates with isocyanates, or, if necessary, esterifying polyurethane compounds obtained by the reaction with (meth) acrylic acid. As specific examples, various commercially available products listed in paragraph 0017 of Japanese Patent Application Laid-Open No. 2007-256844 can be exemplified.

[0392] From the viewpoint of reducing curing shrinkage, as other curable compounds, the hard coat forming composition can also include epoxy compounds having epoxy groups as polymerizable groups. As epoxy compounds, polyfunctional epoxy compounds preferably include more than 2 epoxy groups in one molecule. As specific examples, epoxy compounds described in Japanese Patent Publication No. 2004-264563, Japanese Patent Publication No. 2004-264564, Japanese Patent Publication No. 2005-37737, Japanese Patent Publication No. 2005-37738, Japanese Patent Publication No. 2005-140862, Japanese Patent Publication No. 2005-140862, Japanese Patent Publication No. 2005-140863, Japanese Patent Publication No. 2002-322430 can be cited. In addition, compounds having both epoxy groups and acrylic polymerizable groups such as (meth) glycidyl acrylate are also preferably used.

[0393] From the viewpoint of the hardness of the hard coat layer, when the total solid content of the hard coat layer forming composition is set to 100 mass %, the content of other curable compounds relative to the total solid content of the hard coat layer forming composition is preferably 15 mass % or less, more preferably 10 mass % or less, further preferably 1 mass % or less, further preferably 0.01 mass % or less, and particularly preferably substantially not contained.

[0394] [c) Radical polymerization initiator]

[0395] In the hard coating film according to the present embodiment, the hard coating layer contains 0.1 to 10% by mass of c) a radical polymerization initiator when the total solid content of the hard coating layer is 100% by mass.

[0396] The radical polymerization initiator c) contained in the hard coat layer or the hard coat layer-forming composition in the present embodiment will be described. Hereinafter, the radical polymerization initiator c) will also be referred to as "component c)".

[0397] The polymerization of the compound having an ethylenically unsaturated group can be carried out by irradiation with ionizing radiation or heating in the presence of a photoradical polymerization initiator or a thermal radical polymerization initiator.

[0398] As the photopolymerization initiator and the thermal polymerization initiator, commercially available compounds can be used, which are described in "Latest UV Curing Technology" (p.159, publisher: Kazuhiro Takahashi, publisher: Technical Information Institute Co., Ltd., published in 1991) or the product catalog of Ciba Specialty Chemicals Co., Ltd.

[0399] Specific examples of the component c) include alkylphenol-based photopolymerization initiators (Irgacure 651, Irgacure 184, DAROCURE 1173, Irgacure 2959, Irgacure 127, DAROCURE MBF, Irgacure 907, Irgacure 369, Irgacure 379EG), acylphosphine oxide-based photopolymerization initiators (Irgacure 819, LUCIRIN TPO), and others (Irgacure 784, Irgacure OXE01, Irgacure OXE02, Irgacure 754).

[0400] When the total solid content of the hard coat or the hard coat forming composition in the present embodiment is set to 100% by mass, the addition amount of component c) is in the range of 0.1 to 10% by mass, preferably 1 to 5% by mass, and more preferably 2 to 4% by mass. When the total solid content of the hard coat or the hard coat forming composition is set to 100% by mass, if the addition amount of component c) is 0.1% by mass or more, polymerization will be fully carried out, and the pencil hardness of the hard coat can be improved. On the other hand, when the total solid content of the hard coat or the hard coat forming composition is set to 100% by mass, if the addition amount of component c) is 10% by mass or less, UV light can reach the inside of the film, which can improve the pencil hardness of the hard coat. These c) free radical initiators can be used alone or in combination.

[0401] [d) Cationic polymerization initiator]

[0402] The hard coating film according to the present embodiment contains 0.1 to 10% by mass of d) a cationic polymerization initiator when the total solid content of the hard coating layer is 100% by mass.

[0403] The d) cationic polymerization initiator contained in the hard coat layer or the hard coat layer-forming composition in the present embodiment will be described. Hereinafter, the d) cationic polymerization initiator will also be referred to as "d) component".

[0404] Examples of the component d) include known compounds such as a photoinitiator for photocationic polymerization, a photodecolorizer of a dye type, a photochromic agent, or a known acid generator used in microresists, and mixtures thereof.

[0405] For example, onium compounds, organic halogen compounds, and disulfone compounds are mentioned. Specific examples of the organic halogen compounds and disulfone compounds include the same compounds as those described above for the compound generating free radicals.

[0406] Examples of the onium compound include diazonium salts, ammonium salts, iminium salts, phosphonium salts, iodonium salts, sulfonium salts, arsenic salts, and selenium salts. Examples thereof include compounds described in paragraphs

[0058] to

[0059] of JP-A-2002-29162.

[0407] In the present embodiment, as the cationic polymerization initiator that is particularly preferably used, onium salts can be cited. From the viewpoints of the photosensitivity of photopolymerization initiation, the material stability of the compound, etc., diazonium salts, iodonium salts, sulfonium salts and imide salts are preferred. Among them, iodonium salts are most preferred from the viewpoint of light resistance.

[0408] In the present embodiment, specific examples of onium salts that can be preferably used include acylated sulfonium salts described in paragraph

[0035] of JP-A-9-268205, diaryliodonium salts or triarylsulfonium salts described in paragraphs

[0010] to

[0011] of JP-A-2000-71366, sulfonium salts of S-phenylthiobenzoate described in paragraph

[0017] of JP-A-2001-288205, and onium salts described in paragraphs

[0030] to

[0033] of JP-A-2001-133696.

[0409] Other examples include organic metal / organic halides described in paragraphs

[0059] to

[0062] of JP-A-2002-29162, photoacid generators having an o-nitrobenzyl type protecting group, and compounds that generate sulfonic acid by photolysis (iminosulfonate, etc.).

[0410] As specific compounds of iodonium salt-based cationic polymerization initiators, B2380 (manufactured by Tokyo Chemical Industry Co., Ltd.), BBI-102 (manufactured by Midori Kagaku Co., Ltd.), WPI-113 (manufactured by Wako Pure Chemical Industries, Ltd.), WPI-124 (manufactured by Wako Pure Chemical Industries, Ltd.), WPI-169 (manufactured by Wako Pure Chemical Industries, Ltd.), WPI-170 (manufactured by Wako Pure Chemical Industries, Ltd.), and DTBPI-PFBS (manufactured by Toyo Gosei Kagaku Co., Ltd.) can be used.

[0411] Furthermore, preferred examples of the iodonium salt-based cationic polymerization initiator include the following compounds FK-1 and FK-2.

[0412] Photocationic polymerization initiator (iodonium salt compound) FK-1

[0413] [Chemical formula 5]

[0414]

[0415] Photocationic polymerization initiator (iodonium salt compound) FK-2

[0416] [Chemical formula 6]

[0417]

[0418] As the component d), only one type may be used, or two or more types may be used simultaneously.

[0419] When the total solid content of the hard coat layer or the hard coat layer forming composition in this embodiment is set to 100% by mass, the component d) is added in a range of 0.1 to 10% by mass, preferably 0.5 to 3.0% by mass. From the perspective of the stability of the coating solution, polymerization reactivity, etc., the addition amount is preferably within the above range.

[0420] [e) Inorganic particles reactive with epoxy groups or groups containing ethylenically unsaturated double bonds]

[0421] In the hard coat layer or hard coat layer forming composition of the present embodiment, it is preferred to add e) inorganic particles reactive with epoxy groups or groups containing ethylenically unsaturated double bonds. Hereinafter, e) inorganic particles reactive with epoxy groups or groups containing ethylenically unsaturated double bonds are also referred to as "e) component".

[0422] By adding inorganic particles, the curing shrinkage of the hard coat layer (cured layer) can be reduced, thereby improving the smoothness. In addition, by using inorganic particles reactive with epoxy groups or groups containing ethylenically unsaturated double bonds, the pencil hardness can be increased.

[0423] Examples of the inorganic particles include silica particles, titania particles, zirconia particles, alumina particles, etc. Among them, e) the inorganic particles reactive with an epoxy group or a group containing an ethylenically unsaturated double bond are preferably silica particles.

[0424] In general, inorganic particles have low affinity with organic components such as multifunctional vinyl monomers, so when mixed alone, sometimes agglomerates are formed, or the hard coating after curing is prone to cracking. Therefore, component e) increases the affinity of inorganic particles with organic components, and it is preferred to treat the surface of the inorganic particles with a surface modifier containing an organic segment.

[0425] The surface modifier is preferably a surface modifier having a functional group that forms a bond with inorganic particles or can be adsorbed on inorganic particles and a surface modifier having a functional group with high affinity with organic components in the same molecule. As the surface modifier with the functional group that can be bonded or adsorbed on inorganic particles, the surface modifiers of metal alkoxide surface modifiers such as preferred silane, aluminum, titanium, zirconium or the surface modifiers with anionic groups such as phosphoric acid, sulfuric acid, sulfonic acid, carboxylic acid groups. In addition, as the functional group with high affinity with organic components, although it can be the functional group that only matches the hydrophilicity of organic components, it is preferred that the functional group that can be chemically bonded with organic components, especially preferably the group or the ring-opening polymerizable group comprising olefinic unsaturated double bonds.

[0426] The preferred surface modifier of the inorganic particles in this embodiment is a metal alkoxide or a curable resin having an anionic group and a group containing an ethylenically unsaturated double bond or a ring-opening polymerizable group in the same molecule. By chemically bonding with the organic component, the crosslinking density of the hard coat layer increases, and the pencil hardness can be improved.

[0427] Typical examples of these surface modifiers include the following unsaturated double bond-containing coupling agents, phosphoric acid group-containing organic curable resins, sulfuric acid group-containing organic curable resins, carboxylic acid group-containing organic curable resins, and the like.

[0428] S-1H2C=C(X)COOC3H6Si(OCH3)3

[0429] S-2H2C=C(X)COOC2H4OTi(OC2H5)3

[0430] S-3H2C=C(X)COOC2H4OCOC5H 10 OPO(OH)2

[0431] S-4(H2C=C(X)COOC2H4OCOC5H 10 O)2POOH

[0432] S-5H2C=C(X)COOC2H4OSO3H

[0433] S-6H2C=C(X)COO(C5H 10 COO)2H

[0434] S-7H2C=C(X)COOC5H 10 COOH

[0435] S-8CH2CH(O)CH2OC3H6Si(OCH3)3

[0436] (X represents a hydrogen atom or CH3)

[0437] The surface modification of these inorganic particles is preferably carried out in a solution. When the inorganic particles are mechanically finely dispersed, the following method can be used: a surface modifier is present together, or a surface modifier is added and stirred after the inorganic particles are finely dispersed, and then the surface is modified before the inorganic particles are finely dispersed (heating or pH change after heating or drying as needed), and then finely dispersed. As a solution for dissolving the surface modifier, an organic solvent with large polarity is preferred. Specifically, known solvents such as alcohols, ketones, and esters can be cited.

[0438] Considering the balance between hardness and brittleness of the coating film, the amount of component e) added is preferably 5 to 40% by mass, more preferably 10 to 30% by mass, based on 100% by mass of the total solid content of the hard coat layer or the hard coat layer-forming composition in this embodiment.

[0439] The size (average primary particle size) of the inorganic particles is preferably 10 nm to 100 nm, and more preferably 10 to 60 nm. The average particle size of the particles can be obtained from an electron microscope photograph. If the particle size of the inorganic particles is above the lower limit, the improvement effect of hardness can be obtained, and if it is below the upper limit, the increase in haze can be suppressed.

[0440] The shape of the inorganic particles may be spherical or non-spherical, but from the viewpoint of imparting hardness, non-spherical shapes formed by connecting 2 to 10 inorganic particles are preferred. It is presumed that by using a plurality of inorganic particles connected in a chain, a strong particle network structure is formed, thereby improving hardness.

[0441] Specific examples of the inorganic particles include ELECOM V-8802 (spherical silica particles having an average primary particle size of 12 nm manufactured by JGC Corporation), ELECOM V-8803 (irregular-shaped silica particles manufactured by JGC Corporation), MiBK-SD (spherical silica particles having an average primary particle size of 10 to 20 nm manufactured by NISSAN CHEMICAL INDUSTRIES, LTD.), MEK-AC-2140Z (spherical silica particles having an average primary particle size of 10 to 20 nm manufactured by NISSAN CHEMICAL INDUSTRIES, LTD.), MEK-AC-4130 (spherical silica particles having an average primary particle size of 40 to 50 nm manufactured by NISSAN CHEMICAL INDUSTRIES, LTD.), MiBK-SD-L (spherical silica particles having an average primary particle size of 40 to 50 nm manufactured by NISSAN CHEMICAL INDUSTRIES, LTD.), MEK-AC-5140Z (spherical silica particles having an average primary particle size of 10 to 20 nm manufactured by NISSAN CHEMICAL INDUSTRIES, LTD.), and MEK-AC-6130 (spherical silica particles having an average primary particle size of 40 to 50 nm manufactured by NISSAN CHEMICAL INDUSTRIES, LTD.). Spherical silica particles having an average primary particle size of 70 to 100 nm manufactured by CHEMICAL INDUSTRIES, LTD.) etc. Among them, irregular-shaped ELECOM V-8803 is preferred from the viewpoint of imparting surface hardness.

[0442] [f) Polyester urethane]

[0443] From the viewpoint of improving brittleness, the hard coat layer or the hard coat layer-forming composition in the present embodiment preferably contains f) polyester urethane. Hereinafter, f) polyester urethane is also referred to as "f) component".

[0444] Polyester urethane refers to a polymer containing an ester bond and a urethane bond (—O—CO—NH—) in one molecule.

[0445] f) The polyester urethane is preferably a polyester urethane having a tensile strength of 25 MPa or more and a tensile elongation of 200% or more. It is believed that a polyester urethane having a tensile strength of 25 MPa or more and a tensile elongation of 200% or more can contribute to the high hardness of the hard coating layer and impart appropriate flexibility. It is speculated that this contributes to the high hardness and improved brittleness of the hard coating layer.

[0446] Furthermore, if the polyester carbamate content relative to 100 parts by mass of the total solid content of the hard coat or the hard coat forming composition is 1 part by mass or more, the above-mentioned effect can be fully obtained by adding polyester carbamate, and if it is 10 parts by mass or less, the hardness of the cured layer can be maintained. Therefore, the polyester carbamate content relative to 100 parts by mass of the total solid content of the hard coat or the hard coat forming composition is set in the range of 1 to 10 parts by mass. From the viewpoint of improving brittleness and suppressing the decrease in transparency, it is more preferably 2 parts by mass or more, and from the viewpoint of maintaining the hardness of the hard coat, it is more preferably 8 parts by mass or less.

[0447] As polyester carbamate, a polyester carbamate showing the above-mentioned tensile strength and tensile elongation is used, which helps to simultaneously achieve high hardness and improved brittleness by imparting appropriate softness to the hard coat. The tensile strength is more preferably 40MPa or more, and more preferably 50MPa or more. In addition, from the viewpoint of compatibility stability in the hard coat forming composition, the tensile strength is preferably 70MPa or less. On the other hand, the tensile elongation is preferably 450% or more, and more preferably 600% or more. In addition, from the viewpoint of pencil hardness, which is one of the indicators for ensuring film hardness, the tensile elongation is preferably 1000% or less. The method for determining the pencil hardness will be described later in the examples. The tensile strength and tensile elongation of polyester carbamate are set to the values ​​measured in accordance with JIS K 6251 and using a tensile strength tester.

[0448] Polyester urethane can be obtained by polymerization of monomer components containing at least diol, dicarboxylic acid and diisocyanate. As the three monomers, polyester urethane having a hydroxyl group (-OH), a carboxyl group (-COOH) and an isocyanate group (-NCO) at both ends of a hydrocarbon group having an unbranched structure is preferred.

[0449] The hydrocarbon group having an unbranched structure is preferably an alkylene group, an alkenylene group, an alkynylene group, an arylene group, or a combination thereof.

[0450] The alkylene group, alkenylene group and alkynylene group preferably have a straight chain structure.

[0451] When the hydrocarbon group is an alkylene group, an alkenylene group or an alkynylene group, the number of carbon atoms is preferably 1 to 8, more preferably 2 to 6, and even more preferably 2 to 4.

[0452] The arylene group may have an alkyl group having 1 to 8 carbon atoms as a substituent.

[0453] The arylene group is preferably a phenylene group or a naphthylene group, more preferably a phenylene group, and further preferably a p-phenylene group.

[0454] As the above-mentioned hydrocarbon group, the above-mentioned alkylene group, the above-mentioned arylene group or a combination thereof is particularly preferred.

[0455] As the diol used as a monomer of the polyester urethane, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol and 1,5-pentanediol are preferred.

[0456] As the dicarboxylic acid, terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, succinic acid, glutaric acid, adipic acid, oxalic acid and malonic acid are preferred.

[0457] As the diisocyanate, ethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, m-xylylene diisocyanate, p-phenylene diisocyanate, toluene diisocyanate, p,p′-diphenylmethane diisocyanate and 1,5-naphthylene diisocyanate are preferred.

[0458] The number average molecular weight (Mn) of the polyester urethane is preferably 5,000 or more, more preferably 10,000 or more, from the viewpoint of affinity with inorganic particles, and is preferably 50,000 or less from the viewpoint of compatibility with curable compounds.

[0459] In one embodiment, the polyester urethane may have a reactive group. The reactive group is preferably a polymerizable unsaturated group. Specific examples are the same as those described above for the functional groups that the inorganic particles may have.

[0460] As the polyester urethane described above, polyester urethane synthesized by a known method can be used, or commercial products can be used. Commercial products include VYLON (registered trademark) series (trade name): manufactured by TOYOBO CO., LTD., etc., and VYLON UR-2300, VYLON UR-3200, VYLON UR-3210, VYLON UR-3260, VYLON UR-5537, VYLON UR-8300, VYLON UR-8700, etc. can be preferably used.

[0461] [g) Antifouling agent]

[0462] When the hard coat layer or the hard coat layer-forming composition in the present embodiment contains g) an antifouling agent, it is preferred because the adhesion of fingerprints and dirt can be reduced and the attached dirt can be easily wiped off. It is also preferred from the viewpoint of improving the scratch resistance by improving the smoothness of the surface. Hereinafter, the g) antifouling agent is also referred to as "g) component".

[0463] In the hard coating film according to the present embodiment, it is preferred that g) the antifouling agent contains a fluorine-containing compound having a perfluoropolyether group and a polymerizable unsaturated group and having a plurality of polymerizable unsaturated groups in one molecule.

[0464] g) The antifouling agent that can be used in this embodiment will be described.

[0465] [Fluorinated compound having a polymerizable unsaturated group]

[0466] g) The case where the antifouling agent contains a fluorine-containing compound which is a compound having a perfluoropolyether group and a polymerizable unsaturated group and having a plurality of polymerizable unsaturated groups in one molecule (hereinafter also referred to as a "fluorine-containing antifouling agent") will be described.

[0467] The fluorine-containing antifouling agent is preferably a fluorine-based compound containing a structure represented by the following formula (F).

[0468] Formula (F): (Rf)-[(W)-(R A ) n ] m

[0469] In the formula, Rf represents a (per)fluoroalkyl group or a (per)fluoropolyether group, W represents a connecting group, and R A represents a polymerizable unsaturated group. n represents an integer of 1 to 3. m represents an integer of 1 to 3.

[0470] It is considered that the fluorinated antifouling agent has the following effects (1) to (3) by having a polymerizable unsaturated group.

[0471] (1) It is believed that since the solubility in organic solvents and the compatibility with compounds having unsaturated double bonds are improved, the antifouling agent does not form aggregates but can be uniformly and locally present on the surface. In addition, the generation of defects caused by aggregates can be prevented.

[0472] (2) Even if the fluorinated antifouling agent is locally present on the surface, the fluorinated antifouling agents can form covalent bonds with each other or with a compound having an unsaturated double bond by photopolymerization reaction, thereby preventing the antifouling agent from peeling off due to abrasion and deterioration of antifouling properties.

[0473] (3) It is possible to prevent the loss of antifouling properties and deterioration of appearance caused by the bleeding and precipitation of the antifouling agent.

[0474] In formula (F), R ARepresents a polymerizable unsaturated group. The polymerizable unsaturated group is not particularly limited as long as it is a group that can cause a free radical polymerization reaction by irradiation with active energy rays such as ultraviolet rays or electron rays, and examples thereof include (meth)acryloyl, (meth)acryloyloxy, vinyl, and allyl groups. Preferably, (meth)acryloyl, (meth)acryloyloxy, and any hydrogen atom in these groups is substituted with a fluorine atom.

[0475] As specific examples of the polymerizable unsaturated group, groups having the following structures are preferred.

[0476] [Chemical formula 7]

[0477]

[0478] In formula (F), Rf represents a (per)fluoroalkyl group or a (per)fluoropolyether group.

[0479] Here, the (per)fluoroalkyl group represents at least one of a fluoroalkyl group and a perfluoroalkyl group, and the (per)fluoropolyether group represents at least one of a fluoropolyether group and a perfluoropolyether group. From the viewpoint of antifouling properties, it is preferred that the fluorine content in Rf is high.

[0480] The (per)fluoroalkyl group is preferably a group having 1 to 20 carbon atoms, and more preferably a group having 1 to 10 carbon atoms.

[0481] The (per)fluoroalkyl group may be a straight chain (e.g., -CF2CF3, -CH2(CF2)4H, -CH2(CF2)8CF3, -CH2CH2(CF2)4H, etc.), a branched structure (e.g., CH(CF3)2, CH2CF(CF3)2, CH(CH3)CF2CF3, CH(CH3)(CF2)5CF2H, etc.), or an alicyclic structure (preferably a 5-membered ring or a 6-membered ring, such as perfluorocyclohexyl, perfluorocyclopentyl, or alkyl groups substituted therewith, etc.).

[0482] (Per) fluoropolyether group refers to a (per) fluoroalkyl group having an ether bond, and may be a monovalent or divalent group. Examples of the fluoropolyether group include -CH2OCH2CF2CF3, -CH2CH2OCH2C4F8H, -CH2CH2OCH2CH2C8F 17 , -CH2CH2OCF2CF2OCF2CF2H, a fluorocycloalkyl group having 4 to 20 carbon atoms and having 4 or more fluorine atoms, etc. In addition, examples of the perfluoropolyether group include -(CF2O) p -(CF2CF2O) q -, -[CF(CF3)CF2O] p -[CF2(CF3)]-, -(CF2CF2CF2O) p-、-(CF2CF2O) p -wait.

[0483] The total of p and q is preferably 1-83, more preferably 1-43, and most preferably 5-23.

[0484] From the viewpoint of excellent antifouling properties, the fluorinated antifouling agent preferably has -(CF2O) p -(CF2CF2O) q -represented perfluoropolyether group.

[0485] The above p and q each independently represent an integer of 0 to 20. However, p+q is an integer of 1 or more.

[0486] From the viewpoint of more significantly obtaining the effects shown in (1) to (3) above, the fluorinated antifouling agent preferably has a perfluoropolyether group and has a plurality of polymerizable unsaturated groups in one molecule.

[0487] In formula (F), W represents a linking group. Examples of W include an alkylene group, an arylene group, a heteroalkylene group, or a linking group formed by a combination thereof. These linking groups may further have a functional group such as an oxy group, a carbonyl group, a carbonyloxy group, a carbonylimino group, a sulfonamide group, or a combination thereof.

[0488] As W, an ethylene group is preferred, and an ethylene group bonded to a carbonylimino group is more preferred.

[0489] From the viewpoint of more significantly obtaining the effects shown in (1) to (3) above, in formula (F), the product of n and m (n×m) is preferably 2 or more, and more preferably 4 or more.

[0490] In formula (F), when both n and m are 1, specific examples of the following preferred embodiments include the following formulae (F-1) to (F-3).

[0491] Formula (F-1):

[0492] R 2 (CF2CF2) p R' 2 CH2CH2R 2 OCOCR 1 =CH2

[0493] In formula (F-1), Rf 2 represents a fluorine atom or a fluoroalkyl group having 1 to 10 carbon atoms, R1 represents a hydrogen atom or a methyl group, R 2 represents a single bond or an alkylene group, R' 2 represents a single bond or a divalent linking group, p is an integer representing the degree of polymerization, and the degree of polymerization p is k (k is an integer of 3 or more) or more.

[0494] When R' 2 When a divalent linking group is represented, examples of the divalent linking group include the same linking groups as for W.

[0495] Examples of the telomerization type acrylate containing a fluorine atom in the formula (F-1) include partially or completely fluorinated alkyl ester derivatives of (meth)acrylic acid.

[0496] Specific examples of the compound represented by formula (F-1) are shown below, but the compound is not limited to these compounds.

[0497] [Chemical formula 8]

[0498]

[0499] When the compound represented by the above formula (F-1) is synthesized by using a telomerization reaction, the group Rf of the formula (F-1) may be contained depending on the conditions of the telomerization reaction and the separation conditions of the reaction mixture. 2 (CF2CF2) p R' 2 CH2CH2R 2 O-'s p is a plurality of fluorine-containing (meth)acrylates, wherein k, k+1, k+2, ... are included.

[0500] Formula (F-2):

[0501] F(CF2) q -CH2-CHX-CH2Y

[0502] In formula (F-2), q is an integer of 1 to 20, X and Y are each independently a (meth)acryloyloxy group or a hydroxyl group, and at least one of the (meth)acryloyloxy group is a (meth)acryloyloxy group.

[0503] The fluorine-containing (meth)acrylate represented by the formula (F-2) has a fluoroalkyl group having 1 to 20 carbon atoms and a trifluoromethyl group (CF3-) at the terminal. Even if the fluorine-containing (meth)acrylate is used in a small amount, the trifluoromethyl group can be effectively oriented on the surface.

[0504] From the viewpoint of antifouling property and ease of production, q is preferably 6 to 20, more preferably 8 to 10. Fluorinated (meth)acrylates having fluoroalkyl groups of 8 to 10 carbon atoms also exhibit excellent water / oil repellency compared to fluoroalkyl groups having other chain lengths, and thus have excellent antifouling property.

[0505] Specific examples of the fluorine-containing (meth)acrylate represented by the formula (F-2) include 1-(meth)acryloyloxy-2-hydroxy-4,4,5,5,6,6,7,7,8,8,9,9,10,10,11,11,12,12,13,13,13-heneicofluorotridecane, 2-(meth)acryloyloxy-1-hydroxy-4,4,5,5,6,6,7,7,8,8,9,9,10,10,11,11,12,12,13,13,13-heneicofluorotridecane and 1,2-bis(meth)acryloyloxy-4,4,5,5,6,6,7,7,8,8,9,9,10,10,11,11,12,12,13,13,13-heneicofluorotridecane. In the present embodiment, 1-acryloyloxy-2-hydroxy-4,4,5,5,6,6,7,7,8,8,9,9,10,10,11,11,12,12,13,13,13-heneicofluorotridecane is preferred.

[0506] Formula (F-3):

[0507] F(CF2) r O(CF2CF2O) s CF2CH2OCOCR 3 =CH2

[0508] In formula (F-3), R 3 is a hydrogen atom or a methyl group, s is an integer of 1-20, and r is an integer of 1-4.

[0509] The fluorine-containing monofunctional (meth)acrylate represented by the above formula (F-3) can be obtained by reacting a fluorine-containing alcohol compound represented by the following formula (FG-3) with (meth)acryloyl chloride.

[0510] Formula (FG-3):

[0511] F(CF2) r O(CF2CF2O) s CF2CH2OH

[0512] In the formula (FG-3), s represents an integer of 1-20, and r represents an integer of 1-4.

[0513] Specific examples of the fluorine-containing alcohol compound represented by formula (FG-3) include 1H,1H-perfluoro-3,6-dioxaheptan-1-ol, 1H,1H-perfluoro-3,6-dioxaoctan-1-ol, 1H,1H-perfluoro-3,6-dioxadecan-1-ol, 1H,1H-perfluoro-3,6,9-trioxadecan-1-ol, 1H,1H-perfluoro-3,6,9-trioxaundecane-1-ol, 1H,1H-perfluoro-3,6,9-trioxatridecan-1-ol, 1H,1H-perfluoro-3,6,9,12-tetraoxatridecan-1-ol, 1H,1H-perfluoro-3,6,9,12-tetraoxatridecan-1-ol, 1H,1H-perfluoro-3,6,9,12-tetraoxatetradecane-1-ol, 1H,1H-perfluoro-3,6,9,12-tetraoxatridecan ... Hexadecane-1-ol, 1H,1H-perfluoro-3,6,9,12,15-pentaoxahexadecan-1-ol, 1H,1H-perfluoro-3,6,9,12,15-pentaoxaheptadecan-1-ol, 1H,1H-perfluoro-3,6,9,12,15-pentaoxaheptadecan-1-ol, 1H,1H-perfluoro-3,6,9,12,15-pentaoxaheptadecan-1-ol, 1H,1H-perfluoro-3,6,9,12,15-pentaoxaheptadecan-1-ol, 1H,1H-perfluoro-3,6,9,12,15-pentaoxaheptadecan-1-ol, -hexaoxaicosane-1-ol, 1H,1H-perfluoro-3,6,9,12,15,18-hexaoxadocosan-1-ol, 1H,1H-perfluoro-3,6,9,12,15,18,21-heptaoxatotricosan-1-ol, 1H,1H-perfluoro-3,6,9,12,15,18,21-heptaoxapentacosan-1-ol, and the like.

[0514] These are commercially available, and specific examples thereof include 1H,1H-perfluoro-3,6-dioxaheptan-1-ol (trade name "C5GOL", manufactured by Exfluor Corporation), 1H,1H-perfluoro-3,6,9-trioxadecan-1-ol (trade name "C7GOL", manufactured by Exfluor Corporation), 1H,1H-perfluoro-3,6-dioxadecan-1-ol (trade name "C8GOL", manufactured by Exfluor Corporation), 1H,1H-perfluoro-3,6,9-trioxatridecan-1-ol (trade name "C10GOL", manufactured by Exfluor Corporation), and 1H,1H-perfluoro-3,6,9,12-tetraoxahexadecan-1-ol (trade name "C12GOL", manufactured by Exfluor Corporation).

[0515] In the present embodiment, 1H,1H-perfluoro-3,6,9,12-tetraoxatridecan-1-ol is preferably used.

[0516] Examples of the (meth)acryloyl chloride to be reacted with the fluorine-containing alcohol compound represented by formula (FG-3) include (meth)acryloyl fluoride, (meth)acryloyl chloride, (meth)acryloyl bromide, and (meth)acryloyl iodide. (Meth)acryloyl chloride is preferred from the viewpoint of availability.

[0517] Preferred specific examples of the compound represented by formula (F-3) are shown below, but the present invention is not limited thereto. Preferred specific examples of the compound represented by formula (F-3) are also described in Japanese Unexamined Patent Publication No. 2007-264221.

[0518] (b-1):F9C4OC2F4OC2F4OCF2CH2OCOCH=CH2

[0519] (b-2): F9C4OC2F4OC2F4OCF2CH2OCOC(CH3)=CH2

[0520] In addition to the compound represented by the formula (F-3), a compound represented by the following formula (F-3A) can also be preferably used.

[0521] Formula (F-3A):

[0522] R 3 -[(O) c (O=C) b (CX 4 X 5 ) a -CX 3 =CX 1 X 2 ]

[0523] (Where X 1 and X 2 Each independently represents H or F, X 3 represents H, F, CH3 or CF3, X 4 and X 5 Each independently represents H, F or CF3, a, b and c each independently represent 0 or 1, Rf 3 represents a fluorinated alkyl group having 18 to 200 carbon atoms and containing an ether bond), and in Rf 3 A fluorinated unsaturated compound having 6 or more repeating units represented by the following formula in the base,

[0524] Formula (FG-3A):

[0525] -(CX 6 2CF2CF2O)-

[0526] (Where X 6 is F or H).

[0527] Examples of the fluorine-containing polyether compound represented by the formula (F-3A) include:

[0528] (c-1)Rf 3 -[(O)(O=C) b -CX 3 =CX 1 X 2 ]

[0529] (c-2)Rf 3 -[(O)(O=C)-CX 3 =CX 1 X 2 ]

[0530] (c-3)Rf 3 -[(O) c (O=C)-CF=CH2], etc.

[0531] As the polymerizable unsaturated group of the fluorine-containing polyether compound, a group having the following structure is preferred: The definitions of the symbols in (c-1) to (c-3) are the same as in the formula (F-3A).

[0532] [Chemical formula 9]

[0533]

[0534] Furthermore, the fluorine-containing polyether compound represented by the formula (F-3A) may have a plurality of polymerizable unsaturated groups, and preferably the following structures are mentioned.

[0535] [Chemical formula 10]

[0536]

[0537] In the present embodiment, a compound having a structure of -O(C=O)CF=CH2 is preferred because the polymerization (curing) reactivity is particularly high and a cured product can be obtained efficiently.

[0538] In the fluorinated polyether compound represented by formula (F-3A), Rf 3 It is important that the fluorinated polyether chains of the formula (FG-3A) contain 6 or more fluorinated polyether chains in a repeating unit, thereby imparting antifouling properties.

[0539] Furthermore, in more detail, it may be a mixture of compounds having 6 or more repeating units of a fluorinated polyether chain. When used as a mixture, it is preferably a mixture in which the abundance ratio of the fluorinated unsaturated compound having 6 or more repeating units of the polyether chain is the highest in the distribution of the fluorinated unsaturated compounds having less than 6 repeating units and the fluorinated unsaturated compounds having 6 or more repeating units.

[0540] The repeating units of the fluorinated polyether chain of formula (FG-3A) are preferably 6 or more, more preferably 10 or more, further preferably 18 or more, and particularly preferably 20 or more. Thus, not only the water repellency but also the antifouling property, especially the removability of dirt containing oil components, can be improved. Moreover, air permeability can be further effectively imparted. Furthermore, the fluorinated polyether chain can be in the Rf 3 The moiety may be present at the end of the chain or in the middle of the chain.

[0541] Specifically, Rf 3 The base is preferably

[0542] Formula (c-4):

[0543] R 4 -(CX 6 2CF2CF2O) t -(R 5 ) e -

[0544] (Where X 6 Same as formula (FG-3A), R 4 represents at least one selected from a hydrogen atom, a halogen atom, an alkyl group, a fluorinated alkyl group, an alkyl group containing an ether bond, and a fluorinated alkyl group containing an ether bond, and R 5 represents a divalent or higher valent organic group, t represents an integer of 6 to 66, and e represents 0 or 1. ) structure.

[0545] That is, through a divalent or higher organic group R 5 , bonded to a reactive carbon-carbon double bond and having R at the terminal 4 of fluorinated organic groups.

[0546] R 5 Any organic group may be used as long as it is an organic group that can bond the fluorinated polyether chain of formula (FG-3A) to a reactive carbon-carbon double bond. For example, it is selected from an alkylene group, a fluorinated alkylene group, an alkylene group containing an ether bond, and a fluorinated alkylene group containing an ether bond. Among them, in terms of transparency and low refractive index, a fluorinated alkylene group and a fluorinated alkylene group containing an ether bond are preferred.

[0547] As specific examples of the fluorine-containing polyether compound represented by the formula (F-3A), compounds listed in WO2003 / 022906 are preferably used. In the present embodiment, CH2=CF-COO-CH2CF2CF2-(OCF2CF2CF2)7-OC3F7 can be particularly preferably used.

[0548] In formula (F), when n and m are not 1 at the same time, the following preferred embodiments include formula (F-4) and formula (F-5).

[0549] Formula (F-4): (Rf 1 )-[(W)-(R A ) n ] m

[0550] (In formula (F-4), Rf 1 represents a (per)fluoroalkyl group or a (per)fluoropolyether group, W represents a connecting group, R A It represents a functional group having an unsaturated double bond. n represents an integer from 1 to 3, and m represents an integer from 1 to 3. n and m cannot be 1 at the same time.

[0551] From the viewpoint of excellent water and oil repellency and excellent durability of water and oil repellency (antifouling durability), n is preferably 2-3 and m is 1-3, more preferably n is 2-3 and m is 2-3, and most preferably n is 3 and m is 2-3.

[0552] R 1 Monovalent to trivalent groups can be used. 1 When it is monovalent, as the terminal group, it is preferably (C n F 2n+1 )-、(C n F 2n+1 O)-、(XC n F 2n O)-、(XC n F 2n+1 )-(wherein X is hydrogen, chlorine or bromine, and n is an integer of 1 to 10). Specifically, CF3O(C2F4O) can be preferably used. p CF2-, C3F7O(CF2CF2CF2O) p CF2CF2-, C3F7O(CF(CF3)CF2O) p CF(CF3)-, F(CF(CF3)CF2O) p CF(CF3)-etc.

[0553] Here, the average value of p is 0 to 50, preferably 3 to 30, more preferably 3 to 20, and most preferably 4 to 15.

[0554] When Rf 1 When it is divalent, -(CF2O) can be preferably used. q (C2F4O) r CF2-, -(CF2)3O(C4F8O) r (CF2)3-, -CF2O(C2F4O) r CF2-, -C2F4O(C3F6O) rC2F4-, -CF(CF3)(OCF2CF(CF3)) s OC t F 2t O(CF(CF3)CF2O) r CF(CF3)-etc.

[0555] Here, in the formula, the average value of q, r, and s is 0 to 50, preferably 3 to 30, more preferably 3 to 20, and most preferably 4 to 15. t is an integer of 2 to 6.

[0556] Preferred specific examples and synthesis methods of the compound represented by formula (F-4) are described in International Publication No. 2005 / 113690.

[0557] In the following, F(CF(CF3)CF2O) p Compounds with an average p value of 6 to 7 in CF(CF3)- are recorded as "HFPO-". p Compounds in which the average value of p in CF(CF3)- is 6 to 7 are described as "-HFPO-" to show specific compounds of formula (F-4), but the present invention is not limited to these.

[0558] (d-1):HFPO-CONH-C-(CH2OCOCH=CH2)2CH2CH3

[0559] (d-2): HFPO-CONH-C-(CH2OCOCH=CH2)2H

[0560] (d-3): 1:1 Michael addition polymer of HFPO-CONH-C3H6NHCH3 and trimethylolpropane triacrylate

[0561] (d-4): (CH2=CHCOOCH2)2H-C-CONH-HFPO-CONH-C-(CH2OCOCH=CH2)2H(d-5): (CH2=CHCOOCH2)3-C-CONH-HFPO-CONH-C-(CH2OCOCH=CH2)3

[0562] In addition, as the compound represented by formula (F-4), a compound represented by the following formula (F-5) can also be used.

[0563] Formula (F-5):

[0564] CH2=CX1-COO-CHY-CH2-OCO-CX2=CH2

[0565] (wherein X1 and X2 each independently represent a hydrogen atom or a methyl group, and Y represents a fluoroalkyl group having 2 to 20 carbon atoms and having 3 or more fluorine atoms or a fluorocycloalkyl group having 4 to 20 carbon atoms and having 4 or more fluorine atoms.)

[0566] In this embodiment, the compound whose polymerizable unsaturated group is a (meth)acryloyloxy group may have a plurality of (meth)acryloyloxy groups. When the fluorinated antifouling agent has a plurality of (meth)acryloyloxy groups, a three-dimensional grid structure is presented during curing, the glass transition temperature is high, the transferability of the antifouling agent is low, and the durability against repeated wiping of dirt can be improved. Furthermore, a cured film having excellent heat resistance, weather resistance, etc. can be obtained.

[0567] Specific examples of the compound represented by formula (F-5) include, for example, 2,2,2-trifluoroethylethylene glycol di(meth)acrylate, 2,2,3,3,3-pentafluoropropylethylene glycol di(meth)acrylate, 2,2,3,3,4,4,4-heptafluorobutylethylene glycol di(meth)acrylate, 2,2,3,3,4,4,5,5,5-nonafluoropentylethylene glycol di(meth)acrylate, 2,2,3 , 3,4,4,5,5,6,6,6-undecylfluorohexyl glycol, 2,2,3,3,4,4,5,5,6,6,7,7,7-tridecafluoroheptyl glycol di(meth)acrylate, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluorooctyl glycol di(meth)acrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl glycol di(meth)acrylate diol, di(meth)acrylate-2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,9-heptadecafluorononyl glycol, di(meth)acrylate-2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-nonadecafluorodecyl glycol, di(meth)acrylate-3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-nonadecafluorodecyl glycol, -heptadecafluorodecyl glycol, di(meth)acrylate-2-trifluoromethyl-3,3,3-trifluoropropyl glycol, di(meth)acrylate-3-trifluoromethyl-4,4,4-trifluorobutyl glycol, di(meth)acrylate-1-methyl-2,2,3,3,3-pentafluoropropyl glycol, di(meth)acrylate-1-methyl-2,2,3,3,4,4,4-heptafluorobutyl glycol, etc., can be used alone or as a mixture. Such di(meth)acrylates can be produced by a known method such as that cited in Japanese Patent Publication No. 6-306326. In the present embodiment, di(meth)acrylate-2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,9-heptadecafluorononyl glycol is preferably used.

[0568] In the present embodiment, the compound whose polymerizable unsaturated group is a (meth)acryloyloxy group may be a compound having a plurality of (per)fluoroalkyl groups or (per)fluoropolyether groups in one molecule.

[0569] The fluorine-containing antifouling agent in the present embodiment may be any of a monomer, an oligomer or a polymer.

[0570] The fluorinated antifouling agent preferably further has a substituent that contributes to bond formation or compatibility in the hard coat film. The substituents may be the same or different, and preferably have a plurality of them. Examples of preferred substituents include acryloyl, methacryloyl, vinyl, allyl, cinnamoyl, epoxy, oxetanyl, hydroxyl, polyoxyalkylene, carboxyl, amino, and the like.

[0571] The fluorine-containing antifouling agent may be a polymer with a compound not containing a fluorine atom, or may be an oligomer.

[0572] Furthermore, the fluorine-containing compound may contain a silicon atom, a siloxane structure, or a structure other than a siloxane structure in the molecule. However, when the fluorine-containing compound having a polymerizable unsaturated group contains a siloxane structure, the weight average molecular weight is less than 15,000.

[0573] When the fluorine-containing compound contains a siloxane structure, the fluorine-containing compound is preferably represented by the following formula (F-6).

[0574] Formula (F-6):

[0575] R a R f b R A c SiO (4-a-b-c) / 2

[0576] (wherein, R is a hydrogen atom, a methyl group, an ethyl group, a propyl group or a phenyl group, Rf is an organic group containing a fluorine atom, A is an organic group containing a polymerizable unsaturated group, and 0<a, 0<b, 0<c, a+b+c<4. )

[0577] a is preferably 1 to 1.75, more preferably 1 to 1.5. When a is 1 or more, the synthesis of the compound is easy industrially, and when a is 1.75 or less, both curability and antifouling properties can be easily achieved.

[0578] As R A The polymerizable unsaturated group in the formula (F) may be A The same polymerizable unsaturated group is preferably a (meth)acryloyl group, a (meth)acryloyloxy group, and a group in which any hydrogen atom in these groups is substituted with a fluorine atom.

[0579] When the fluorine-containing compound contains a siloxane structure, as a preferred example of the siloxane structure, there can be cited a structure having a substituent at the end and / or side chain of a compound chain containing multiple dimethylsilyloxy units as repeating units. The compound chain containing dimethylsilyloxy as a repeating unit may also contain structural units other than dimethylsilyloxy. The substituents may be the same or different, and preferably have multiple substituents. As examples of preferred substituents, there can be cited groups including (meth)acryloyl, (meth)acryloyloxy, vinyl, allyl, cinnamoyl, epoxy, oxetanyl, hydroxyl, fluoroalkyl, polyoxyalkylene, carboxyl, amino, etc., and from the viewpoint of inhibiting the seepage of the antifouling agent, (meth)acryloyloxy is particularly preferred. And, as for the number of substituents, from the viewpoint of improving the partiality of the antifouling agent and inhibiting the seepage, the functional group equivalent is preferably 1500 to 20000 g·mol -1 .

[0580] R f is an organic group containing a fluorine atom, preferably C x F 2x+1 (CH2) p - (wherein x is an integer of 1 to 8, and p is an integer of 2 to 10.) or a perfluoropolyether substituted alkyl group. b is preferably 0.2 to 0.4, more preferably 0.2 to 0.25. If b is 0.2 or more, the antifouling property is improved, and if b is 0.4 or less, the curing property is improved. R f A perfluoroalkyl group having 8 carbon atoms is preferred.

[0581] R A It is an organic group containing a (meth) acrylic group, and from the viewpoint of industrial ease of synthesis, the bond to the Si atom is preferably a Si-OC bond. c is preferably 0.4 to 0.8, more preferably 0.6 to 0.8, and when it is 0.4 or more, the curability is improved, and when it is 0.8 or less, the antifouling property is improved.

[0582] Furthermore, a+b+c is preferably 2 to 2.7, more preferably 2 to 2.5. If it is less than 2, localization on the surface is likely to occur, and if it is greater than 2.7, there is a tendency that both curability and antifouling properties cannot be achieved.

[0583] When the fluorine-containing compound contains a siloxane structure, the fluorine-containing compound contains 3 or more F atoms and 3 or more Si atoms in one molecule, preferably 3 to 17 F atoms and 3 to 8 Si atoms. If the number of F atoms is 3 or more, the antifouling property becomes sufficient, and if the number of Si atoms is 3 or more, the partialization on the surface can be promoted, and the antifouling property becomes sufficient.

[0584] When the fluorine-containing compound contains a siloxane structure, the fluorine-containing compound can be produced using a known method such as that listed in Japanese Patent Application Laid-Open No. 2007-145884.

[0585] When the fluorine-containing compound contains a siloxane structure, the siloxane structure may be any of linear, branched, and cyclic structures. Among these, compounds having a branched or cyclic structure are particularly preferred because they have good compatibility with the compounds having unsaturated double bonds described later, have no repulsion, and easily cause partial localization on the surface.

[0586] Here, as the compound having a branched siloxane structure, a compound represented by the following formula (F-7) is preferred.

[0587] Formula (F-7):

[0588] R f S i k 〔OSiR m (OR A ) 3-m 〕 3-k

[0589] (In the formula, R, R f , R A Same as above, m=0, 1 or 2, especially m=2, k=0 or 1. )

[0590] Furthermore, as the compound whose siloxane structure is a cyclic structure, a compound represented by the following formula (F-8) is preferred.

[0591] Formula (F-8):

[0592] (R f RSiO)(R A RSiO) n (In the formula, R, Rf, R A Same as above, n≥2, especially 3≤n≤5.)

[0593] Specific examples of such fluorine-containing polysiloxane compounds include the following compounds.

[0594] [Chemical formula 11]

[0595]

[0596] The weight average molecular weight (Mw) of the fluorinated antifouling agent can be measured using molecular exclusion chromatography, such as gel permeation chromatography (GPC) and the like. The Mw of the fluorinated antifouling agent used in the present embodiment is preferably 400 or more and less than 5000, more preferably 1000 or more and less than 5000, and further preferably 1000 or more and less than 3500. If Mw is 400 or more, the surface mobility of the antifouling agent becomes high, so it is preferred. And, if Mw is less than 5000, the surface mobility of the fluorinated antifouling agent will not be hindered during the process from coating to curing, and it is easy to be uniformly oriented on the surface of the hard coat, so antifouling and film hardness are improved, so it is preferred.

[0597] However, when the fluorine-containing compound contains a siloxane structure, Mw is less than 15,000, preferably 1,000 or more and less than 5,000, and more preferably 1,000 or more and less than 3,500.

[0598] The amount of the fluorinated antifouling agent added is preferably 1 to 20% by mass, more preferably 1 to 15% by mass, and further preferably 1 to 10% by mass relative to the total solid content in the hard coat or hard coat forming composition. If the amount of the fluorinated antifouling agent added is 1% by mass or more relative to the total solid content in the hard coat or hard coat forming composition, the proportion of the antifouling agent having water and oil repellency becomes appropriate, and sufficient antifouling properties can be obtained. In addition, if the amount of the fluorinated antifouling agent added is 20% by mass or less relative to the total solid content in the hard coat or hard coat forming composition, the antifouling agent that cannot be mixed with the resin component will not precipitate on the surface, the film will not be bleached, or white powder will not be generated on the surface, so it is preferred.

[0599] The fluorine atom content of the fluorine-containing antifouling agent is not particularly limited, but is preferably 20% by mass or more, particularly preferably 30 to 70% by mass, and most preferably 40 to 70% by mass.

[0600] Preferred examples of fluorine-containing antifouling agents include R-2020, M-2020, R-3833, M-3833, and OPTOOL DAC (these are trade names) manufactured by Daikin Industries Ltd., and MEGAFACE F-171, F-172, F-179A, DEFENSA MCF-300, and MCF-323 (these are trade names) manufactured by DIC Corporation, but are not limited to these.

[0601] [Polysiloxane compound having a polymerizable unsaturated group and a weight average molecular weight of 15,000 or more]

[0602] Next, the polysiloxane compound having a polymerizable unsaturated group and a weight average molecular weight of 15000 or more which can be used as the component g) is described. In addition, the polysiloxane compound having a molecular weight of 15000 or more is hereinafter referred to as a "polysiloxane antifouling agent".

[0603] One embodiment of a preferred example of the polysiloxane antifouling agent is a compound represented by the above formula (F-6).

[0604] Preferred examples of polysiloxane antifouling agents include compounds having substituents at the ends and / or side chains of a compound chain containing multiple dimethylsiloxy units as repeating units. The compound chain containing dimethylsiloxy as a repeating unit may also contain structural units other than dimethylsiloxy. The substituents may be the same or different, and preferably have multiple substituents. Examples of preferred substituents include (meth)acryloyl, (meth)acryloyloxy, vinyl, allyl, cinnamoyl, epoxy, oxetanyl, hydroxyl, fluoroalkyl, polyoxyalkylene, carboxyl, amino and the like. In terms of suppressing the seepage of the antifouling agent, (meth)acryloyloxy is particularly preferred. In addition, as for the number of substituents, from the perspective of improving the partiality of the antifouling agent and suppressing the seepage, the functional group equivalent is preferably 1500 to 20000 g·mol. -1 .

[0605] The polysiloxane antifouling agent is preferably a compound containing 3 or more F atoms and 3 or more Si atoms, preferably 3 to 17 F atoms and 3 to 8 Si atoms in one molecule. If it contains 3 or more F atoms, the antifouling property becomes sufficient, and if it contains 3 or more Si atoms, localization on the surface can be promoted, and the antifouling property becomes sufficient.

[0606] The polysiloxane antifouling agent can be produced using a known method such as that listed in JP-A-2007-145884.

[0607] As the additive having a polysiloxane structure, it is also preferable to add a polysiloxane containing a reactive group {e.g., "KF-100T", "X-22-169AS", "KF-102", "X-22-3701IE", "X-22-164C", "X-22-5002", "X-22-173B", "X-22-174D", "X-22-167B", "X-22-161AS" (trade names), all manufactured by Shin-Etsu Chemical Co., Ltd.; "AK-5", "AK-30", "AK-32" (trade names), all manufactured by TOAGOSEI CO., LTD.; "SILAPLANE FM0725", "SILAPLANE FM0721" (trade names), all manufactured by JNC Corporation; "DMS-U22", "RMS-033", "UMS-182" (trade names), all manufactured by Gelest, etc. In addition, silicone compounds described in Table 2 or Table 3 of Japanese Patent Application Laid-Open No. 2003-112383 can also be preferably used.

[0608] The siloxane structure contained in the polysiloxane antifouling agent may be any of a linear, branched, or cyclic structure, but among these, compounds having a branched or cyclic structure are particularly preferred because they have good compatibility with the compounds having unsaturated double bonds described later, have no repulsion, and easily cause localization on the surface.

[0609] The weight average molecular weight of the polysiloxane antifouling agent is 15,000 or more, preferably 15,000 or more and 50,000 or less, and more preferably 18,000 or more and 30,000 or less. If the weight average molecular weight of the polysiloxane antifouling agent is less than 15,000, the surface localization of the polysiloxane is reduced, thereby causing deterioration of antifouling properties and a decrease in hardness, which is not preferred from this point of view. However, when the fluorine-containing compound having a polymerizable unsaturated group has a polysiloxane structure, the above problem does not occur.

[0610] The weight average molecular weight of the polysiloxane antifouling agent can be measured using size exclusion chromatography, for example, gel permeation chromatography (GPC) or the like.

[0611] The amount of the polysiloxane antifouling agent added is preferably 1% by mass or more and less than 25% by mass, more preferably 1% by mass or more and less than 20% by mass, further preferably 1% by mass or more and less than 15% by mass, and most preferably 1% by mass or more and less than 10% by mass, relative to the total solid content in the hard coat or hard coat forming composition. If the amount of the polysiloxane antifouling agent added is 1% by mass or more, the proportion of the antifouling agent with water and oil repellency becomes appropriate, and sufficient antifouling properties can be obtained. In addition, if the amount of the polysiloxane antifouling agent added is less than 25% by mass, the antifouling agent that cannot be mixed with the resin component will not precipitate on the surface, the film will not be bleached, or white powder will not be generated on the surface, so it is preferred.

[0612] Regarding the distribution state of the antifouling agent in the film thickness direction in the hard coating layer, when X is set to the fluorine amount or silicone amount near the surface of the hard coating layer, and Y is set to the fluorine amount or silicone amount of the entire hard coating layer, it is preferred to satisfy 51%<X / Y<100%. When X / Y is greater than 51%, the antifouling agent is not distributed inside the film of the hard coating layer, so it is preferred from the perspective of antifouling properties and film hardness. In addition, the vicinity of the surface refers to an area less than 1 μm deep from the surface of the hard coating layer, which can be measured by time-of-flight secondary ion mass spectrometry (TOF-SIMS). - Fragment or Si2C5H 15 O + The ratio of the fragments was determined.

[0613] g) The antifouling agent is preferably an antifouling agent that is soluble in a liquid or solvent at 20° C. The solvent can be appropriately selected according to the polarity of the compound, but is preferably an organic solvent that is miscible with dimethyl carbonate, and examples thereof include aliphatic or aromatic alcohols, ketones, esters, and ether solvents. It is particularly preferred if it is soluble in dimethyl carbonate.

[0614] Regarding the surface tension of the antifouling agent g) from the viewpoint of antifouling properties, the surface tension is preferably 25.0 mN / m or less, more preferably 23.0 mN / m or less, and even more preferably 16.0 mN / m or less.

[0615] The surface tension of the antifouling agent is the surface tension in a single film, and can be measured as follows.

[0616] (Method for measuring surface tension of antifouling agent)

[0617] An antifouling agent was spin-coated on a quartz substrate, and when it contained a solvent, it was dried to produce a film. Next, a contact angle meter ["CA-X" contact angle meter, manufactured by Kyowa Interface Science Co., Ltd.] was used, and pure water was used as the liquid to make a droplet of 1.0 mm in diameter on a needle in a dry state (20°C / 65% RH), and the droplet was made in contact with the surface of the spin-coated film to produce a droplet on the film. The angle formed by the tangent line relative to the liquid surface at the contact point between the film and the liquid and the film surface, that is, the angle on the side containing the liquid, was set as the contact angle and measured. In addition, methylene iodide was used instead of water to measure the contact angle, and the surface free energy was calculated using the following formula.

[0618] Refer to DK Owens: J. Appl. Polym. Sci., 13, 1741 (1969), and the contact angles θ of pure water H2O and methylene iodide CH2I2 obtained experimentally on an antireflection film H2O ,θ CH2I2 And use the following simultaneous equations a and b to find γs d With γs h The value represented by the sum γs v (=γs d +γs h ) to the surface free energy (γs v : Unit, mN / m) is defined.

[0619] a.1+cosθ H2O =2√γs d (√γ H2O d / γ H2O v )+2√γs h (√γ H2O h / γ H2O v )

[0620] b.1+cosθ CH2I2 =2√γs d (√γ CH2I2 d / γ CH212 v )+2√γs h (√γ CH212 h / γ CH2I2 v )

[0621] γ H2o d =21.8,γ H2o h=51.0,γ H2O v =72.8,

[0622] γ CH2I2 d =49.5,γ CH2I2 h =1.3,γ CH2I2 v =50.8

[0623] As the antifouling agent g) described above, a compound synthesized by a known method may be used, or a commercially available product may be used. As the commercially available product, RS-90 and RS-78 manufactured by DIC Corporation may be preferably used.

[0624] (Solvent)

[0625] The hard coat forming composition in the present embodiment may contain a solvent. As the solvent, various solvents selected from viewpoints such as being able to dissolve or disperse each component, being easy to become a uniform planar shape in a coating process and a drying process, being able to ensure solution preservation and having a suitable saturated vapor pressure can be used.

[0626] The solvent may be a mixture of two or more solvents. In particular, from the viewpoint of drying load, it is preferred to use a solvent having a boiling point of 100° C. or less at normal pressure and room temperature as a main component and to contain a small amount of a solvent having a boiling point exceeding 100° C. in order to adjust the drying rate.

[0627] In the hard coat layer forming composition of the present embodiment, in order to prevent the sedimentation of particles, the total solvent of the coating composition preferably contains 30 to 80% by mass of a solvent having a boiling point of 80° C. or less, and more preferably contains 50 to 70% by mass. By setting the ratio of the solvent having a boiling point of 80° C. or less to the above ratio, the penetration of the resin component into the polyester film can be appropriately suppressed, and the sedimentation of particles can be suppressed by increasing the viscosity increase rate due to drying.

[0628] Examples of solvents having a boiling point of 100°C or less include hydrocarbons such as hexane (boiling point 68.7°C), heptane (98.4°C), cyclohexane (80.7°C), and benzene (80.1°C); halogenated hydrocarbons such as dichloromethane (39.8°C), chloroform (61.2°C), carbon tetrachloride (76.8°C), 1,2-dichloroethane (83.5°C), and trichloroethylene (87.2°C); and ethers such as diethyl ether (34.6°C), diisopropyl ether (68.5°C), dipropyl ether (90.5°C), and tetrahydrofuran (66°C). esters such as ethyl formate (54.2°C), methyl acetate (57.8°C), ethyl acetate (77.1°C), and isopropyl acetate (89°C); ketones such as acetone (56.1°C) and 2-butanone (same as methyl ethyl ketone, MEK, 79.6°C); alcohols such as methanol (64.5°C), ethanol (78.3°C), 2-propanol (82.4°C), and 1-propanol (97.2°C); cyano compounds such as acetonitrile (81.6°C) and propionitrile (97.4°C); carbon disulfide (46.2°C), etc. Among them, ketones and esters are preferred, and ketones are particularly preferred. Among ketones, 2-butanone is particularly preferred.

[0629] Examples of the solvent having a boiling point exceeding 100° C. include octane (125.7° C.), toluene (110.6° C.), xylene (138° C.), tetrachloroethylene (121.2° C.), chlorobenzene (131.7° C.), dioxane (101.3° C.), dibutyl ether (142.4° C.), isobutyl acetate (118° C.), cyclohexanone (155.7° C.), 2-methyl-4-pentanone (same as MIBK, 115.9° C.), 1-butanol (117.7° C.), N,N-dimethylformamide (153° C.), N,N-dimethylacetamide (166° C.), and dimethyl sulfoxide (189° C.). Cyclohexanone and 2-methyl-4-pentanone are preferred.

[0630] (Surfactant)

[0631] In the hard coat layer or the hard coat layer forming composition in the present embodiment, various surfactants and / or wind spot preventing agents (hereinafter collectively referred to as surfactants) are also preferably used. Generally speaking, surfactants and / or wind spot preventing agents can suppress uneven film thickness caused by drying deviation caused by local distribution of dry wind.

[0632] Specifically, the surfactant preferably contains a fluorine-based surfactant or a silicone-based surfactant or both. Furthermore, the surfactant is more preferably an oligomer or a polymer rather than a low molecular weight compound.

[0633] Preferred examples of fluorine-based surfactants include copolymers containing fluorinated aliphatic groups (hereinafter sometimes referred to as "fluorine-based polymers"). Among the above-mentioned fluorine-based polymers, useful ones are copolymers of acrylic resins, methacrylic resins and vinyl monomers copolymerizable therewith, which contain repeating units of a monomer corresponding to the following (i), or contain repeating units of a monomer corresponding to the following (i) and repeating units of a monomer corresponding to the following (ii).

[0634] (i) A fluorinated aliphatic group-containing monomer represented by the following formula (i):

[0635] Formula (i)

[0636] [Chemical formula 12]

[0637]

[0638] In formula (i), R 11 represents a hydrogen atom or a methyl group, and X represents an oxygen atom, a sulfur atom or -N(R 12 )-, m represents an integer of 1 to 6, and n represents an integer of 2 to 4. 12 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, specifically, represents a methyl group, an ethyl group, a propyl group, or a butyl group, and preferably represents a hydrogen atom or a methyl group. X is preferably an oxygen atom.

[0639] (ii) a monomer represented by the following formula (ii) copolymerizable with the above (i)

[0640] Formula (ii)

[0641] [Chemical formula 13]

[0642]

[0643] In formula (ii), R 13 represents a hydrogen atom or a methyl group, and Y represents an oxygen atom, a sulfur atom or -N(R 15 )-,R 15 It represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, specifically, it represents a methyl group, an ethyl group, a propyl group, or a butyl group, and is preferably a hydrogen atom or a methyl group. Y is preferably an oxygen atom, -N(H)-, or -N(CH3)-.

[0644] R 14 represents a linear, branched or cyclic alkyl group having 4 to 20 carbon atoms which may have a substituent. 14The substituent of the alkyl group may include, but is not limited to, hydroxyl, alkylcarbonyl, arylcarbonyl, carboxyl, alkylether, arylether, fluorine, chlorine, bromine, and other halogen atoms, nitro, cyano, and amino groups. As the straight-chain, branched, or cyclic alkyl group having 4 or more and 20 or less carbon atoms, it is preferred to use butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, and eicosyl groups, which may have straight chains and branches, and monocyclic cycloalkyl groups such as cyclohexyl and cycloheptyl, and polycyclic cycloalkyl groups such as bicycloheptyl, bicyclodecyl, tricycloundecyl, tetracyclododecyl, adamantyl, norbornyl, and tetracyclodecyl groups.

[0645] The amount of the fluorinated aliphatic group-containing monomer represented by formula (i) used in the fluorinated polymer is 10 mol% or more, preferably 15 to 70 mol%, more preferably 20 to 60 mol%, based on the monomers of the fluorinated polymer.

[0646] The preferred mass average molecular weight of the fluorine-based polymer is preferably 3000 to 100,000, more preferably 5,000 to 80,000. In addition, the preferred amount of the fluorine-based polymer added is in the range of 0.001 to 5 parts by mass relative to 100 parts by mass of the coating liquid, more preferably in the range of 0.005 to 3 parts by mass, and further preferably in the range of 0.01 to 1 part by mass. If the amount of the fluorine-based polymer added is 0.001 parts by mass or more, the effect of adding the fluorine-based polymer can be fully obtained, and if it is 5 parts by mass or less, there will be no problem of not being able to fully dry the coating or having a bad effect on the performance of the coating.

[0647] Examples of preferred silicone compounds include X-22-174DX, X-22-2426, X22-164C, and X-22-176D (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd.; FM-7725, FM-5521, and FM-6621 (all trade names) manufactured by JNC Corporation; DMS-U22 and RMS-033 (all trade names) manufactured by Gelest; SH200, DC11PA, ST80PA, L7604, FZ-2105, L-7604, Y-7006, and SS-2801 (all trade names) manufactured by Dow Corning Toray Co., Ltd.; and TSF400 (trade name) manufactured by Momentive Performance Materials Japan, but the present invention is not limited thereto.

[0648] When the total solid content of the hard coat layer forming composition in the present embodiment is 100% by mass, the silicone-based surfactant is preferably contained in an amount of 0.01 to 0.5% by mass, and more preferably 0.01 to 0.3% by mass.

[0649] (matt particles)

[0650] For the purpose of imparting internal scattering properties or imparting surface irregularities, the hard coat layer or the hard coat layer-forming composition may contain matte particles having an average particle size of 1.0 to 15.0 μm, preferably 1.5 to 10.0 μm. In addition, in order to adjust the viscosity of the coating liquid, a polymer compound or an inorganic layered compound may be contained. e) may also be used as matte particles.

[0651] The hard coating film involved in one embodiment of the present invention may include other layers (arbitrary layers) in addition to the polyester film and hard coating layer involved in the above-mentioned embodiment. As such arbitrary layers, for example, an easy-adhesion layer, an anti-reflection layer (a laminated film of one or more high-refractive index layers and one or more low-refractive index layers), an anti-glare layer, an antistatic layer, etc. can be cited, but are not limited to these. For these arbitrary layers, for example, reference can be made to paragraphs 0069 to 0091 of Japanese Patent Gazette No. 5048304. In addition, a decorative layer may be provided in the hard coating film involved in this embodiment.

[0652] Examples of preferred layer structures of the hard coat film according to the present embodiment are shown below, but the hard coat film is not particularly limited to these layer structures.

[0653] Polyester film / hard coating

[0654] ·Polyester film / hard coating / low refractive index layer

[0655] Polyester film / hard coating / anti-glare layer (antistatic layer) / low refractive index layer,

[0656] Polyester film / hard coating / anti-glare layer / antistatic layer / low refractive index layer,

[0657] Polyester film / hard coating / antistatic layer / anti-glare layer / low refractive index layer,

[0658] Polyester film / hard coating (antistatic layer) / anti-glare layer / low refractive index layer,

[0659] Polyester film / hard coating / high refractive index layer / antistatic layer / low refractive index layer,

[0660] Polyester film / hard coating / high refractive index layer (antistatic layer) / low refractive index layer,

[0661] Polyester film / hard coating / antistatic layer / high refractive index layer / low refractive index layer,

[0662] Polyester film / hard coating / medium refractive index layer / high refractive index layer (antistatic layer) / low refractive index layer,

[0663] ·Polyester film / hard coating / medium refractive index layer (antistatic layer) / high refractive index layer / low refractive index layer,

[0664] Polyester film / hard coating (antistatic layer) / medium refractive index layer / high refractive index layer / low refractive index layer,

[0665] ·Polyester film / antistatic layer / hard coating / medium refractive index layer / high refractive index layer / low refractive index layer,

[0666] · Antistatic layer / polyester film / hard coating / medium refractive index layer / high refractive index layer / low refractive index layer,

[0667] Among them, the antistatic layer and the anti-glare layer may have hard coating properties.

[0668] (Low refractive index layer)

[0669] In the hard coating film of this embodiment, a low refractive index layer can be formed on the hard coating layer for the purpose of imparting a reflectivity reduction effect. The low refractive index layer has a lower refractive index than the hard coating layer and has a thickness of preferably 50 to 200 nm, more preferably 70 to 150 nm, and most preferably 80 to 120 nm.

[0670] The refractive index of the low refractive index layer is lower than that of the layer directly therebelow, and is preferably 1.20 to 1.55, more preferably 1.25 to 1.46, and particularly preferably 1.30 to 1.40.

[0671] The thickness of the low refractive index layer is preferably 50 to 200 nm, more preferably 70 to 100 nm.

[0672] The low refractive index layer is preferably obtained by curing a curable composition for forming a low refractive index layer.

[0673] As a preferred embodiment of the curable composition for the low refractive index layer,

[0674] The following can be cited:

[0675] (1) A composition containing a fluorine-containing compound having a crosslinkable or polymerizable functional group,

[0676] (2) A composition containing a hydrolysis condensate of a fluorine-containing organosilane material as a main component,

[0677] (3) A composition comprising a monomer having two or more ethylenically unsaturated groups and inorganic particles (particularly preferably inorganic particles having a hollow structure).

[0678] The compositions of (1) and (2) above also preferably contain inorganic particles. In particular, the use of inorganic particles having a hollow structure with a low refractive index is preferred from the viewpoint of lowering the refractive index or adjusting the amount of inorganic particles added and the refractive index.

[0679] (1) Composition containing a fluorine-containing compound having a crosslinkable or polymerizable functional group

[0680] Examples of the fluorine-containing compound having a crosslinkable or polymerizable functional group include copolymers of a fluorine-containing monomer and a monomer having a crosslinkable or polymerizable functional group, namely, fluorine-containing polymers. Specific examples of these fluorine-containing polymers are described in Japanese Patent Application Publication Nos. 2003-222702 and 2003-183322.

[0681] In addition, the above-mentioned fluorine-containing polymer can be used simultaneously with a curing agent that suitably has a polymerizable unsaturated group as described in Japanese Patent Laid-Open No. 2000-17028. In addition, it is also preferably used simultaneously with a compound having a fluorine-containing multifunctional polymerizable unsaturated group as described in Japanese Patent Laid-Open No. 2002-145952. As an example of a compound with a multifunctional polymerizable unsaturated group, a monomer with more than 2 ethylenically unsaturated groups described as a curable resin compound of the above-mentioned low-refractive index layer can be cited. In addition, it is also preferred that the hydrolysis condensate of the organosilane described in Japanese Patent Laid-Open No. 2004-170901 is hydrolyzed, and it is particularly preferred that the organosilane hydrolysis condensate containing (methyl) acryloyl is hydrolyzed. When these compounds are used in particular in a polymer main body with a compound having a polymerizable unsaturated group, the effect of using the improved scratch resistance is large, so it is preferred.

[0682] When the polymer itself does not have sufficient curability alone, the required curability can be imparted by blending a crosslinking compound. For example, when the polymer body contains a hydroxyl group, various amino compounds are preferably used as curing agents. The amino compound used as a crosslinking compound is, for example, a compound containing a total of two or more hydroxyalkylamino groups and any one or two of alkoxyalkylamino groups, and specifically, for example, melamine compounds, urea compounds, benzoguanamine compounds, glycoluril compounds, etc. are cited. Organic acids or salts thereof are preferably used in the curing of these compounds.

[0683] (2) Compositions containing a hydrolysis condensate of a fluorine-containing organosilane material as a main component

[0684] Compositions with hydrolyzed condensates of fluorinated organosilane compounds as main components have low refractive index and high hardness of coating surface, so they are preferred. Condensates of compounds containing hydrolyzable silanol at one or both ends of fluorinated alkyl and tetraalkoxysilane are preferred. Specific compositions are described in Japanese Patent Publication No. 2002-265866 and Japanese Patent Publication No. 317152.

[0685] (3) Composition containing a monomer having two or more ethylenically unsaturated groups and inorganic particles having a hollow structure

[0686] As another preferred mode, a low refractive index layer composed of low refractive index particles and resin can be cited. As low refractive index particles, they can be organic or inorganic, but preferably have particles with pores inside. As a specific example of hollow particles, silica particles described in Japanese Patent Publication No. 2002-79616 can be cited. The particle refractive index is preferably 1.15 to 1.40, and more preferably 1.20 to 1.30. As resin, monomers with two or more ethylenically unsaturated groups described in the above-mentioned anti-glare layer page can be cited.

[0687] The composition for forming a low refractive index layer used in the present embodiment preferably contains a photoradical polymerization initiator or a thermal radical polymerization initiator. When a radical polymerizable compound is contained, 1 to 10 parts by mass, preferably 1 to 5 parts by mass of the polymerization initiator can be used relative to the compound.

[0688] Inorganic particles can be used together with the low refractive index layer used in this embodiment. In order to impart scratch resistance, particles having a particle size of 15% to 150%, preferably 30% to 100%, and more preferably 45% to 60% of the thickness of the low refractive index layer can be used.

[0689] To the low refractive index layer used in the present embodiment, a known silicone or fluorine-based antifouling agent, lubricant, etc. may be appropriately added for the purpose of imparting properties such as antifouling properties, water resistance, chemical resistance, and slip properties.

[0690] As an additive having a polysiloxane structure, it is also preferred to add a polysiloxane containing a reactive group {for example, KF-100T, X-22-169AS, KF-102, X-22-37-01IE, X-22-164B, X-22-5002, X-22-173B, X-22-174D, X-22-167B, X-22-161AS (trade names), all manufactured by Shin-Etsu Chemical Co., Ltd.; AK-5, AK-30, AK-32 (trade names), all manufactured by TOAGOSEI CO., LTD.; "SILAPLANE FM0725", "SILAPLANE FM0721" (trade names), all manufactured by JNC Corporation, etc.}. Furthermore, silicone compounds described in Table 2 and Table 3 of JP-A-2003-112383 can also be preferably used.

[0691] As fluorine compounds, compounds having a fluoroalkyl group are preferred. The number of carbon atoms in the fluoroalkyl group is preferably 1 to 20, more preferably 1 to 10, and may be a straight chain (e.g., -CF2CF3, -CH2(CF2)4H, -CH2(CF2)8CF3, -CH2CH2(CF2)4H, etc.), a branched structure (e.g., CH(CF3)2, CH2CF(CF3)2, CH(CH3)CF2CF3, CH(CH3)(CF2)5CF2H, etc.), an alicyclic structure (preferably a 5-membered ring or a 6-membered ring, such as a perfluorocyclohexyl group, a perfluorocyclopentyl group, or an alkyl group substituted therewith, etc.), or an ether bond (e.g., CH2OCH2CF2CF3, CH2CH2OCH2C4F8H, CH2CH2OCH2CH2C8F 17 , CH2CH2OCF2CF2OCF2CF2H, etc.). A plurality of the above fluoroalkyl groups may be contained in the same molecule.

[0692] The fluorine compound preferably further has a substituent that contributes to the bond formation or compatibility with the low refractive index layer film. The above-mentioned substituents may be the same or different, and preferably have a plurality of them. Examples of preferred substituents include acryloyl, methacryloyl, vinyl, aryl, cinnamoyl, epoxy, oxetanyl, hydroxyl, polyoxyalkylene, carboxyl, amino, etc. The fluorine compound may be a polymer with a compound that does not contain fluorine atoms, or may be an oligomer, and the molecular weight is not particularly limited. The fluorine atom content of the fluorine compound is not particularly limited, but is preferably 20% by mass or more, particularly preferably 30 to 70% by mass, and most preferably 40 to 70% by mass. Examples of preferred fluorine compounds include R-2020, M-2020, R-3833, M-3833, OPTOOL DAC (these are trade names) manufactured by Daikin Industries Ltd., MEGAFACE F-171, F-172, F-179A, DEFENSA MCF-300, MCF-323 (these are trade names) manufactured by DIC Corporation, but are not limited to these.

[0693] These polysiloxane fluorine compounds or compounds having a polysiloxane structure are preferably added in an amount of 0.1 to 10% by mass, and particularly preferably 1 to 5% by mass, based on the total solid content of the low refractive index layer.

[0694] [Method for applying hard coat layer]

[0695] The hard coat layer according to the hard coat film of the present invention can be formed by the following method.

[0696] First, a hard coat forming composition is prepared. Then, the composition is applied to a polyester film (substrate film) by dip coating, air knife coating, curtain coating, rod coating, wire rod coating, gravure coating, die coating, etc., and heated / dried. More preferably, micro gravure coating, wire rod coating, die coating (with reference to U.S. Patent No. 2681294 specification, Japanese Patent Publication No. 2006-122889), especially preferably die coating.

[0697] After the hard coating layer is applied on the substrate film, it is transported in the form of a web to an area heated for drying the solvent. The temperature of the drying area at this time is preferably 25°C to 140°C, preferably the first half of the drying area is relatively low temperature, and the second half is relatively high temperature. However, it is preferably below the temperature at which the components other than the solvent contained in the coating composition of each layer begin to volatilize. For example, among the commercially available photoradical generators used simultaneously with ultraviolet curing resins, there are also photoradical generators that volatilize about several tens of percent in a few minutes in warm air at 120°C, and there are also monofunctional and bifunctional acrylate monomers that volatilize in warm air at 100°C. In this case, as described above, it is preferably below the temperature at which the components other than the solvent contained in the coating composition of the hard coating layer begin to volatilize.

[0698] Furthermore, regarding the drying wind after applying the hard coat coating composition on the substrate film, in order to prevent uneven drying, the wind speed on the coating film surface is preferably in the range of 0.1 to 2 m / sec while the solid content concentration of the coating composition is 1 to 50%.

[0699] Furthermore, after the coating composition of the hard coat layer is applied onto the substrate film, if the temperature difference between the conveying roller in contact with the opposite surface of the coated surface of the substrate film in the drying area and the substrate film is within 0°C to 20°C, it is possible to prevent uneven drying caused by uneven heat conduction on the conveying roller, and therefore it is preferred.

[0700] After the solvent is dried, the sheet is passed through an area where the hard coat layer is cured by irradiation with ionizing radiation to cure the coating. For example, if the coating is UV-curable, it is preferably irradiated with an ultraviolet lamp at 10 mJ / cm 2 ~1000mJ / cm 2 The coating is cured by irradiating ultraviolet rays with an irradiation amount of 50%. At this time, the irradiation amount distribution in the width direction of the sheet is preferably 50 to 100% including both ends relative to the maximum irradiation amount in the center, and more preferably 80 to 100%. In addition, when it is necessary to purge nitrogen gas or the like to reduce the oxygen concentration in order to promote surface curing, the oxygen concentration is preferably 0.01% to 5%, and the distribution in the width direction is preferably 2% or less in terms of oxygen concentration. In the case of ultraviolet irradiation, ultraviolet rays emitted from light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, xenon arc lamps, and metal halide lamps can be used. In addition, in order to promote the curing reaction, the temperature can also be increased during curing, preferably 25 to 100°C, more preferably 30 to 80°C, and most preferably 40 to 70°C.

[0701] Furthermore, other functional layers can be provided as required. When other functional layers are stacked in addition to the hard coat layer, multiple layers can be applied simultaneously or one by one. The manufacturing method of these layers can be carried out according to the manufacturing method of the hard coat layer.

[0702] The use of the polyester film according to the present embodiment is not particularly limited, but the polyester film can be preferably used for uses that require suppression of the generation of recesses when a load is applied.

[0703] The polyester film according to the present embodiment can be preferably used as a base film for various functional films such as a sensor film for a touch panel, an anti-scattering film, and an anti-reflection film, in addition to a base film for a hard coat film.

[0704] [Anti-scattering film]

[0705] The anti-scattering film according to the present embodiment is an anti-scattering film in which an adhesive layer is laminated on at least one side of the polyester film according to the present embodiment. The polyester film according to the present embodiment can be used for the anti-scattering film. The anti-scattering film preferably has a hard coating layer and an adhesive layer laminated on the polyester film.

[0706] The adhesive layer can be formed by either wet coating or dry coating. When forming the adhesive layer, an acrylic adhesive composition such as a solvent-based acrylic polymer or a solvent-based acrylic resin syrup, a solvent-free acrylic resin syrup, or a solvent-free urethane acrylate can be used.

[0707] [Anti-reflective film]

[0708] The antireflection film according to the present embodiment is an antireflection film in which an antiglare layer is laminated on at least one surface of the polyester film according to the present embodiment. The polyester film according to the present embodiment can be used for the antireflection film.

[0709] The anti-glare layer can be formed by any method of a wet coating method or a dry coating method. The anti-glare layer can use the anti-glare layer described in Japanese Patent Application Laid-Open No. 2014-059334, Japanese Patent Application Laid-Open No. 2014-026122, Japanese Patent Application Laid-Open No. 2014-016602, Japanese Patent Application Laid-Open No. 2014-016476, Japanese Patent Application Laid-Open No. 2014-041206, Japanese Patent Application Laid-Open No. 2014-032317, Japanese Patent Application Laid-Open No. 2014-026123, and Japanese Patent Application Laid-Open No. 2014-010316.

[0710] [Sensor films for touch panels]

[0711] The touch panel sensor film according to the present embodiment is a touch panel sensor film including the polyester film according to the present embodiment. The polyester film according to the present embodiment can be used for a touch panel sensor film. The touch panel sensor film preferably has a hard coating layer and a transparent conductive layer stacked on the polyester film.

[0712] As a general method for forming the transparent conductive layer, there are PVD (Physical Vapor Deposition) methods such as sputtering, vacuum evaporation, and ion plating, or CVD (Chemical Vapor Deposition) methods, coating methods, printing methods, etc. In addition, there is no particular limitation on the material for forming the transparent conductive layer, and examples thereof include indium tin composite oxide (ITO), tin oxide, copper, silver, aluminum, nickel, chromium, etc., and different materials can be overlapped to form the transparent conductive layer.

[0713] In addition, a primer layer for improving transparency or optical properties is sometimes provided before forming the transparent conductive layer. In addition, a metal layer composed of a single metal element or an alloy of two or more metal elements is sometimes provided between the primer layer and the polyester film in order to improve adhesion. The metal layer is preferably a metal selected from the group consisting of silicon, titanium, tin and zinc.

[0714] [Image display device]

[0715] The image display device according to the present embodiment includes an image display element and the hard coat film according to the present embodiment, and the hard coat film is disposed on the outermost surface.

[0716] Examples of the image display device according to the present embodiment include a liquid crystal display device (LCD), a plasma display panel, an electroluminescent display, and a cathode ray tube display device.

[0717] Examples of liquid crystal display devices include TN (Twisted Nematic) type, STN (Super-Twisted Nematic) type, TSTN (Triple Super Twisted Nematic) type, multi-domain type, VA (Vertical Alignment) type, IPS (In Plane Switching) type, and OCB (Optically Compensated Bend) type.

[0718] The image display device particularly includes a liquid crystal cell and the polarizing plate according to the present embodiment disposed on at least one surface of the liquid crystal cell, and preferably a liquid crystal display device in which the hard coat film according to the present embodiment is disposed on the outermost surface. In this case, the image display element is a liquid crystal display element.

[0719] In the image display device according to the present embodiment, it is also preferable that the image display element is an organic electroluminescent display element.

[0720] [Touch panel]

[0721] The touch panel according to the present embodiment includes the hard coat film according to the present embodiment, and the hard coat film is disposed on the outermost surface.

[0722] The touch panel to which the hard coating film according to the present embodiment can be applied is not particularly limited and can be appropriately selected according to the purpose. For example, a surface-type electrostatic capacitive touch panel, a projection-type electrostatic capacitive touch panel, a resistive film touch panel, etc. can be cited. The details will be described later as the resistive film touch panel according to the present embodiment and the electrostatic capacitive touch panel according to the present embodiment.

[0723] In addition, the touch panel includes so-called touch sensors and touch pads. The layer structure of the touch panel sensor electrode portion in the touch panel can be any of a bonding method of bonding two transparent electrodes, a method of having transparent electrodes on both sides of a substrate, a one-side bridging or through-hole method, or a one-side stacking method. Moreover, the projection type electrostatic capacitive touch panel is preferably driven by AC (Alternating Current) rather than DC (Direct Current) drive, and a driving method in which the voltage application time to the electrode is short is more preferred.

[0724] (Resistive film touch panel)

[0725] The resistive film type touch panel according to the present embodiment is a resistive film type touch panel including the hard coating film according to the present embodiment.

[0726] The resistive touch panel has a basic structure in which a pair of upper and lower substrates having conductive films are arranged so as to face each other via a spacer. The structure of the resistive touch panel is well known, and the well-known technology can be applied to the present embodiment without any limitation.

[0727] (Capacitive touch panel)

[0728] The capacitive touch panel according to the present embodiment is a capacitive touch panel including the hard coat film according to the present embodiment.

[0729] As the mode of electrostatic capacitive touch panel, surface electrostatic capacitive, projection electrostatic capacitive, etc. can be cited. The projection type electrostatic capacitive touch panel is composed of a basic structure in which an X-axis electrode and a Y-axis electrode orthogonal to the X-axis electrode are configured via an insulator. As a specific mode, a mode in which X electrodes and Y electrodes are formed on each surface of a substrate, a mode in which an X electrode, an insulator layer, and a Y electrode are sequentially formed on a substrate, a mode in which an X electrode is formed on a substrate, and a mode in which a Y electrode is formed on another substrate (in this mode, the structure of bonding two substrates becomes the above-mentioned basic structure), etc. can be cited. In addition, the structure of the electrostatic capacitive touch panel is well known, and in this embodiment, the well-known technology can be applied without any restrictions.

[0730] Example

[0731] Below, enumerate embodiment and comparative example and the present invention is further specifically described.As long as the material, usage amount, ratio, processing content, processing step etc. shown in the following examples do not depart from the purpose of the present invention, then can be appropriately changed.Therefore, the scope of the present invention should not be interpreted restrictively by the specific example shown below.

[0732] In addition, unless otherwise specified, "parts" and "ppm" are based on mass.

[0733] [Example 1]

[0734] <Synthesis of Raw Material Polyester>

[0735] (Raw material polyester 1)

[0736] As shown below, terephthalic acid and ethylene glycol were directly reacted to remove water by distillation, and then esterification was performed. Then, a direct esterification method of polycondensation under reduced pressure was used to obtain a raw material polyester 1 (Sb catalyst-based PET) using a continuous polymerization apparatus.

[0737] (1) Esterification reaction

[0738] 4.7 tons of high-purity terephthalic acid and 1.8 tons of ethylene glycol were mixed to form a slurry over 90 minutes and continuously supplied to the first esterification reaction tank at a flow rate of 3800 kg / h. Ethylene glycol solution of antimony trioxide was continuously supplied, and the reaction was carried out at a temperature of 250°C in the reaction tank under stirring for an average residence time of about 4.3 hours. At this time, antimony trioxide was continuously added so that the amount of Sb added was 150 ppm in terms of element conversion value.

[0739] The reactant was transferred to the second esterification reaction tank, and reacted under stirring at a temperature of 250° C. in the reaction tank for an average residence time of 1.2 hours. An ethylene glycol solution of magnesium acetate and an ethylene glycol solution of trimethyl phosphate were continuously supplied to the second esterification reaction tank so that the Mg addition amount and the P addition amount were 65 ppm and 35 ppm, respectively, in terms of element conversion values.

[0740] (2) Polycondensation reaction

[0741] The esterification reaction product obtained above was continuously supplied to the first polycondensation reaction tank, and the reaction was carried out under stirring at a reaction temperature of 270°C and a pressure of 20 torr (2.67×10 -3 MPa), and the polycondensation was carried out with an average residence time of about 1.8 hours.

[0742] Then the mixture was transferred to the second polycondensation reaction tank, where the mixture was stirred at a temperature of 276°C and a pressure of 5 torr (6.67×10 -4 MPa) and a residence time of about 1.2 hours, and the reaction (polycondensation) was carried out.

[0743] Next, the mixture was transferred to the third polycondensation reaction tank, where the temperature inside the reaction tank was 278°C and the pressure inside the reaction tank was 1.5 torr (2.0×10 -4 MPa) and a residence time of 1.5 hours to carry out a reaction (polycondensation) to obtain a reactant (polyethylene terephthalate; PET)).

[0744] Next, the obtained reaction product was sprayed into cold water in a strand shape and immediately cut to produce polyester pellets (cross section: long diameter about 4 mm, short diameter about 2 mm, length: about 3 mm).

[0745] The obtained polyester had IV = 0.63. This polyester was designated as raw material polyester 1.

[0746] <Manufacturing of polyester film>

[0747] -Film forming process-

[0748] The raw polyester 1 was dried to a moisture content of 20 ppm or less and then fed into a hopper 1 of a single screw kneading extruder 1 having a diameter of 50 mm. The raw polyester 1 was melted at 300° C. and extruded from a die through a gear pump and a filter (pore size 20 μm) under the following extrusion conditions.

[0749] The extrusion conditions of the molten resin were set to 1% pressure variation and 2% temperature distribution of the molten resin to extrude the molten resin from the die. Specifically, the back pressure was increased by 1% relative to the average pressure in the barrel of the extruder and the pipe temperature of the extruder was set to a temperature 2% higher than the average temperature in the barrel of the extruder.

[0750] The molten resin extruded from the die was extruded onto a cooling casting drum set at a temperature of 25° C. and was brought into close contact with the cooling casting drum by electrostatic application. The unstretched polyester film 1 was obtained by peeling with a peeling roll disposed opposite to the cooling casting drum.

[0751] -Formation of easy-adhesion layer-

[0752] The following compounds were mixed at the following ratio to prepare an easily adhesive layer-forming coating liquid H1.

[0753] (Coating liquid H1 for forming an easily adhesive layer)

[0754]

[0755] The details of the compound used for forming the easy-adhesion layer are shown below.

[0756] Polyester resin: (IC)

[0757] Sulfonic acid aqueous dispersion of polyester resin obtained by copolymerization of monomers of the following composition

[0758] Monomer composition: (acid component) terephthalic acid / isophthalic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%)

[0759] Acrylic resin: (II)

[0760] Aqueous dispersion of acrylic resin obtained by polymerizing monomers of the following composition

[0761] Emulsified polymer of ethyl acrylate / n-butyl acrylate / methyl methacrylate / N-hydroxymethyl acrylamide / acrylic acid = 65 / 21 / 10 / 2 / 2 (mass %) (emulsifier: anionic surfactant)

[0762] Melamine compounds: (VIB) hexamethoxymethylmelamine

[0763] Particles: (VII) Silica sol having an average particle size of 150 nm (the average particle size refers to a primary average particle size, i.e., an average value of primary particle sizes.)

[0764] -Coating of an easy-adhesion layer on one side of a polyester film-

[0765] By the bar coating method using a wire bar, the easily adhesive layer-forming coating liquid H1 was applied to one side of the unstretched polyester film 1 using a wire bar while adjusting the coating film thickness after stretching to be 65 nm.

[0766] - Transverse stretching process -

[0767] The unstretched polyester film 1 was introduced into a tenter (transverse stretching machine), and the film was transversely stretched by the following method and conditions while the ends of the film were held with clips.

[0768] (Preheating section)

[0769] The film was heated with hot air so that the surface temperature at the start of stretching became 89°C.

[0770] The surface temperature at the start of stretching was measured at the center of the film in the width direction at the start of stretching using a radiation thermometer (manufactured by Hayashi Denko Co., Ltd., model: RT61-2, used with an emissivity of 0.95).

[0771] (Stretching section)

[0772] The preheated unstretched polyester film 1 was stretched in the transverse direction (TD) using a tenter under the following conditions while being heated with hot air.

[0773] The surface temperature at each stretching ratio was measured at the center of the film width direction using a radiation thermometer (manufactured by Hayashi Denko Co., Ltd., model: RT61-2, used with an emissivity of 0.95).

[0774] <Conditions>

[0775] · Transverse stretching ratio: 4.1 times

[0776] Surface temperature at 2x stretching: 90°C

[0777] Surface temperature at 3 times stretching: 94°C

[0778] Surface temperature at the end of stretching: 95°C

[0779] (Heat setting part and heat relaxation part)

[0780] Next, hot air was blown toward the film from a hot air blowing nozzle from the upper and lower directions relative to the film, and the polyester film was subjected to heat setting and heat relaxation while the surface temperature thereof was controlled within the following range.

[0781] <Conditions>

[0782] Maximum surface temperature (heat setting temperature): 185°C

[0783] Thermal relaxation rate: MD4%, TD1.5%

[0784] (Cooling section)

[0785] Next, the film was cooled by blowing cold air from a cold air blowing nozzle toward the film from the upper and lower directions relative to the film. The film was cooled so that the surface temperature of the film became 40° C. when released from the clips of the tenter.

[0786] The surface temperature was measured at the center of the film in the width direction using a radiation thermometer (manufactured by Hayashi Denko Co., Ltd., model: RT61-2, used at an emissivity of 0.95).

[0787] (Film recycling)

[0788] After cooling and releasing the film from the clamp, the polyester film was trimmed by 20 cm at both ends. The film width after trimming was 2 m. After that, the two ends were extruded (knurled) with a width of 10 mm, and the film of 10,000 m in length was rolled into a roll at a tension of 18 kg / m.

[0789] As described above, the polyester film of Example 1 having a thickness of 200 μm and wound into a roll was produced.

[0790] [Examples 2 to 11, 13, 14, Comparative Examples 1 to 3, 5]

[0791] In Example 1, polyester films of each of Examples and Comparative Examples were produced in the same manner as in Example 1 except that the conditions of the transverse stretching step, the adhesive layer, and the hard coat layer were changed as described in Table 1 below.

[0792] [Example 12, Comparative Example 4]

[0793] A polyester film of Example 12 was produced in the same manner as in Example 1 except that the easy-adhesion layer was not provided.

[0794] Furthermore, the polyester film of Comparative Example 4 was produced in the same manner as in Example 1, except that the conditions of the transverse stretching step and the film thickness were changed as described in Table 1 below, and no easy-adhesion layer was provided. In Comparative Example 4, a polyester film was produced by a similar method based on the description of Example 2 of Japanese Patent Application Laid-Open No. 2012-230390.

[0795] [Thin film measurement results]

[0796] The following physical properties were measured for the films obtained in each example. The measurement results are shown in Table 1 below.

[0797] <Thickness>

[0798] The thicknesses of the polyester films obtained in each of the examples and comparative examples were determined as follows.

[0799] For the polyester films of each of the examples and comparative examples, using a contact type film thickness gauge (manufactured by Anritsu Corporation), 50 points were sampled at equal intervals over 0.5 m in the longitudinal stretching direction (length direction), and then 50 points were sampled at equal intervals (the film was equally divided into 50 parts in the width direction) over the entire width of the film in the film width direction (the direction orthogonal to the length direction). After that, the thicknesses at these 100 points were measured. The average thickness of these 100 points was determined as the thickness of the polyester film.

[0800] <Re, Rth, Re / Rth ratio>

[0801] For the films obtained in each example, Re and Rth were determined by the aforementioned method. The Re / Rth ratio was calculated based on the obtained Re and Rth.

[0802] <Shearing plane perpendicular stress and shearing plane yield stress>

[0803] For the polyester films of each of the examples and comparative examples obtained, using the SAICAS-NN type (manufactured by DAIPLA WINTESCO., LTD.), the shearing plane perpendicular stress and shearing plane yield stress of the 1-μm surface layer of the film were measured by the aforementioned method, respectively.

[0804] Based on the obtained measured values, the average value of the shearing plane perpendicular stress A in the slow axis direction at the 1-μm surface layer and the shearing plane perpendicular stress B in the direction orthogonal to the slow axis direction (fast axis direction) in the film plane was calculated. In addition, TD is the slow axis direction of the film, and MD is the fast axis direction of the film.

[0805] [Production of hard coating film]

[0806] A coating liquid for forming a hard coating having the following composition was prepared.

[0807]

[0808]

[0809] [Chemical formula 14]

[0810]

[0811] The uniaxially stretched polyester films of the examples and comparative examples that were wound up in a roll form were unwound, and as a post-process, the hard coat layer-forming coating liquid was applied by the following method.

[0812] The coating liquid for forming a hard coating layer was applied to one side of the film (the side of the easy-adhesion layer when an easy-adhesion layer was provided) at a conveying speed of 30 m / min by the die coating method using a slit die as described in Example 1 of Japanese Patent Publication No. 2006-122889. After drying at 60° C. for 150 seconds, the film was irradiated with an illumination of 400 mW / cm2 using an air-cooled metal halide lamp (manufactured by EYE GRAPHICS Co., Ltd.) at an oxygen concentration of about 0.1% and a nitrogen purge. 2 、Irradiation 500mJ / cm 2 The coating layer (hard coating layer) was cured by ultraviolet rays and then wound up.

[0813] <Film thickness of hard coat>

[0814] When the polyester films obtained in the examples or comparative examples other than Example 9 were used, the thickness of the hard coat layer was set to 22 μm, and when the polyester film obtained in Example 9 was used, the thickness of the hard coat layer was set to 5 μm.

[0815] The film thickness of the hard coat layer was calculated by measuring the film thickness of the produced hard coat layer with a contact-type film thickness meter and subtracting the thickness of the polyester film measured in the same manner from the film thickness.

[0816] [evaluate]

[0817] The hard coating films obtained in each of the Examples and Comparative Examples were evaluated as follows. The evaluation results are shown in Table 1 below.

[0818] <Punching Evaluation>

[0819] The hard coating film was punched out 10 times, and the cracking / peeling state of the hard coating film at the punched end surface was evaluated according to the following criteria.

[0820] A: No cracking or peeling

[0821] B: Only one crack / peeling occurred

[0822] C: Only 2 to 3 cracks / peelings occurred

[0823] D: More than 4 cracks / peelings occurred

[0824] <Surface deformation evaluation>

[0825] Observe the hard coating surface (hard coating side) with a stylus at 10N / mm 2The following criteria were used to evaluate the depression when the mold was pressed with a force of 1.58kV.

[0826] A: No dents at all

[0827] B: Although the depression cannot be seen with the naked eye, it can be identified under a microscope.

[0828] C: The depression is slightly visible to the naked eye

[0829] D: The depression can be clearly seen with the naked eye

[0830] <Visibility Evaluation>

[0831] The hard coat film was sandwiched between polarizing plates provided in crossed polarizers so that the orientation angle was inclined at 45° with respect to the absorption axis of the polarizing plates, and LED backlight was irradiated from behind, and visibility was evaluated based on the following criteria.

[0832] A: No rainbow unevenness can be observed

[0833] B: Rainbow unevenness is hardly observed

[0834] C: A little rainbow unevenness can be observed, but it is tolerable

[0835] D: Rainbow-like unevenness is clearly observed

[0836]

[0837] The meanings of the symbols in Table 1 are as follows.

[0838] DPHA: KAYARD DPHA (manufactured by Nippon Kayaku Co., Ltd.)

[0839] ·3,4-EpoxyCHMA: 3,4-Epoxycyclohexyl methacrylate

[0840] ·3,4-EpoxyCHMM: 3,4-Epoxycyclohexylmethyl methacrylate

[0841] IRG127: Irgacure127 (alkyl phenone photopolymerization initiator, manufactured by BASF)

[0842] IRG290: Irgacure 290 (sulfonium salt-based cationic polymerization initiator, manufactured by BASF)

[0843] RS-90: (Antifouling agent, manufactured by DIC Corporation)

[0844] As is clear from Table 1, the hard coating films of Examples were less prone to cracking and peeling of the hard coating layer and to depressions than the hard coating films of Comparative Examples.

[0845] The entire disclosure of Japanese Patent Application No. 2016-026351 filed on February 15, 2016 is incorporated herein by reference.

[0846] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical standard were specifically and individually set forth by reference.

[0847] Explanation of symbols

[0848] 10- cutting blade, 12- polyester film, 20- jig (holding member).

Claims

1. A polyester film having a thickness of 40 to 500 μm, wherein the average value of the shear plane perpendicular stress A in the slow axis direction at 1 μm from the surface layer and the shear plane perpendicular stress B in the direction perpendicular to the slow axis direction in the film surface is 30 to 100 MPa. 2 . The polyester film according to claim 1 , which is a film for a base film of a hard coat film. The polyester film according to claim 1 or 2, which is a uniaxially oriented polyester film.

4. The polyester film according to any one of claims 1 to 3, wherein The polyester film has a retardation Re within a film plane at a measurement wavelength of 589 nm of 4,000 to 50,000 nm.

5. The polyester film according to any one of claims 1 to 4, wherein The average value of the shear plane yield stress in the slow axis direction at 1 μm in the surface layer of the polyester film and the shear plane yield stress in the direction perpendicular to the slow axis direction in the film surface is 20 to 60 MPa.

6. The polyester film according to any one of claims 1 to 5, wherein The ratio of the shear plane vertical stress A to the shear plane vertical stress B is 1.1 to 2.

0.

7. The polyester film according to any one of claims 1 to 6, wherein The polyester film has a ratio of retardation Re within a film plane at a measurement wavelength of 589 nm to retardation Rth in a film thickness direction of 0.6 to 1.

2.

8. A hard coating film having: A substrate film comprising the polyester film according to any one of claims 1 to 7; and The hard coating layer is laminated on at least one side of the base film.

9. The hard coating film according to claim 8, wherein The hard coating layer has a thickness of 5 μm or more.

10. The hard coating film according to claim 8 or 9, wherein The hard coating layer at least includes a structure derived from the following a), a structure derived from the following b), the following c) and the following d), When the total solid content of the hard coating layer is 100% by mass, the hard coating layer contains 15 to 70% by mass of a structure derived from the following a), 25 to 80% by mass of a structure derived from the following b), 0.1 to 10% by mass of the following c), and 0.1 to 10% by mass of the following d), a) a compound having one alicyclic epoxy group and one group containing an ethylenically unsaturated double bond in the molecule and having a molecular weight of 300 or less; b) a compound having three or more groups containing ethylenically unsaturated double bonds in the molecule; c) a free radical polymerization initiator; d) Cationic polymerization initiator. 11 . An image display device comprising an image display element and the hard coating film according to claim 8 , wherein the hard coating film is disposed on the outermost surface. 12 . A touch panel comprising the hard coating film according to claim 8 , wherein the hard coating film is disposed on the outermost surface.

13. A method for producing a polyester film, the method producing a polyester film having a thickness of 40 to 500 μm, using a transverse stretching device having a plurality of clamps, the plurality of clamps respectively moving along a pair of rails arranged on both sides of a film conveying path, The manufacturing method comprises: A preheating process, preheating the unstretched or longitudinally stretched polyester film at a heating rate of less than 600°C / min; a transverse stretching step, in which the preheated polyester film is stretched in a direction perpendicular to the film conveying path while holding both edges of the preheated polyester film with the plurality of clamps, the surface temperature of the polyester film is gradually increased from the start of the transverse stretching to the end of the transverse stretching, the surface temperature at the start of the transverse stretching is controlled to be 80° C. to 95° C., and the surface temperature at the end of the transverse stretching is controlled to be 90° C. to 105° C., and the transverse stretching ratio is controlled to be within a range of 3.3 times to 4.8 times; and The heat setting step is to heat the polyester film after the transverse stretching step to a maximum temperature in the transverse stretching device to perform heat setting.

14. The method for producing a polyester film according to claim 13, wherein: In the transverse stretching step, the surface temperature is gradually increased at a heating rate of 60° C. / min or less. The surface temperature is controlled to be 80° C. to 92° C. when the transverse stretching ratio is in the range of 1 to 2. The surface temperature is controlled to be 85° C. to 97° C. when the transverse stretching ratio is in the range of 2 times or more and less than 3 times, and The surface temperature is controlled to be 90° C. or higher and 102° C. or lower when the transverse stretch ratio is in the range of 3 times or higher.

15. The method for producing a polyester film according to claim 13 or 14, wherein: The rate of increase in the surface temperature of the polyester film from the end of the transverse stretching step to the maximum temperature in the heat setting step is controlled to be 1000° C. / min or less, The highest surface temperature of the polyester film in the heat setting step is controlled to be 130° C. or higher and 230° C. or lower, and the time during which the surface temperature of the polyester film exceeds 130° C. is controlled to be 180 seconds or less. 16 . The method for producing a polyester film according to claim 13 , further comprising a heat relaxation step of heating the polyester film after the heat setting step to reduce at least a lateral length of the polyester film.

17. A method for producing a hard coating film, comprising: A step of manufacturing a polyester film by the method for manufacturing a polyester film according to any one of claims 13 to 16; and A step of laminating a hard coating layer on at least one side of the polyester film.

Citation Information

Patent Citations

  • divan base with swivel frame

    CH20519A

  • brush with watering device

    CH20520A

  • pulley

    CH20565A

  • JP1974062661A

  • JP1975048304A